Ultraviolet laser printing paper, printed material and method for manufacturing same, processed

Ultraviolet laser printing paper with optimized titanium oxide content and crystallite size addresses high costs and clarity issues in existing printing technologies, providing clear and dust-free printing.

CN119212873APending Publication Date: 2024-12-27OJI HLDG CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202380040201.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-07
Filing Date
2023-05-16
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing methods for printing on packages using thermal printers, inkjet printers, or UV curing ink result in high costs due to expensive consumables, potential printing leakage, and issues with clarity and visibility, while laser printing technologies face limitations in material compatibility and environmental pollution from dust.

Method used

Ultraviolet laser printing paper with a specific content and crystallite size of titanium oxide on a paper substrate, optimized for clear printing with a sealing and barrier layer, and an ink composition that changes color upon laser irradiation.

Benefits of technology

Achieves clear and visible printing dots with reduced dust generation and improved visibility, addressing the limitations of existing methods by enhancing print clarity and reducing environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005131850650000412
    Figure BDA0005131850650000412
  • Figure BDA0005131850650000701
    Figure BDA0005131850650000701
  • Figure BDA0005131850650000711
    Figure BDA0005131850650000711
Patent Text Reader

Abstract

The present invention addresses the problem of providing: a substrate; provided are: a sheet for ultraviolet laser printing which, when irradiated with an ultraviolet laser, provides print dots having excellent print clarity per dot; a printed matter in which the sheet for ultraviolet laser printing is irradiated with an ultraviolet laser to change the color of the irradiated region; a method for producing the printed matter; and an ink composition which is used in the production of the sheet for ultraviolet laser printing. Also provided is a processed article obtained using the sheet for ultraviolet laser printing or a printed matter. This paper for ultraviolet laser printing has a printing layer containing titanium oxide on a paper substrate, the content of the titanium oxide in the printing layer being 0.1 g / m2 or more, and the crystallite size of the titanium oxide in the printing layer being 30 nm or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to ultraviolet laser printing paper, printed matter, and a method for producing the same, a processed product, and an ink composition. Background Art

[0002] Conventionally, label marking or inkjet printing has been performed to mark dates such as the date of manufacture and the date of shipment, or variable information such as a barcode, on packaging such as a container for storing stored items.

[0003] In addition, a method of printing by laser irradiation has also been proposed. For example, in order to provide a laser printing laminate and a printed body thereof that can perform clear printing at high speed by laser irradiation and has excellent various resistances of the printed part, a laser printing laminate is disclosed, which is manufactured by coating white ink, black ink and overprint varnish (OP varnish) on the aluminum-plated surface of aluminum-plated paper.

[0004] Furthermore, in order to provide a technology for laser marking of packaging materials with relatively less heat generation, Patent Document 2 describes an ink composition for forming a laser marking layer that changes color upon irradiation with ultraviolet laser, the ink composition comprising first titanium oxide particles having an average particle size of less than 150 nm.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 9-123607

[0008] Patent Document 2: Japanese Patent Application Publication No. 2020-75943 Summary of the invention

[0009] Problem that the invention aims to solve

[0010] As a means of printing on the surface of a package, label, adhesive tape, etc., there is a method of using a thermal printer or inkjet printer to directly place ink on the surface of the package, which is currently commonly used. However, consumables such as the ink ribbon of a thermal printer and the ink of an inkjet printer are expensive, and there is a problem that the running cost becomes expensive in order to print a large amount of variable information. In addition, if these consumables are not replaced, printing leakage may occur. Furthermore, direct printing of variable information on the package based on offset printing using UV curing ink is also carried out, but due to contaminants on the surface of the package and uneven thickness of the package, printing is sometimes blurred or text is missing.

[0011] In addition, the method described in Patent Document 1 is a technology that can achieve high speed, but removes the upper layer that easily absorbs laser light by irradiation of CO2 laser, exposes the lower layer, and forms visible text and the like by the color difference between the upper layer and the lower layer. Therefore, the upper layer is limited to materials that easily absorb laser light, while the lower layer is not easy to absorb laser light and is limited to materials that obtain color contrast with the upper layer. That is, the carbon black-based material (black) that easily absorbs laser light becomes the upper layer, and the titanium oxide-based material (white) becomes the lower layer, and the text and the like formed by irradiation of laser light become white text on a black background, and visibility is poor. In addition, when removing the upper layer, there is a problem that the toner of the upper layer becomes dusty, causing pollution to the working environment.

[0012] Furthermore, when printing is performed using an ultraviolet laser on a coating layer produced using the ink composition described in Patent Document 2, the print clarity of each printed dot may vary.

[0013] The object of the present invention is to provide ultraviolet laser printing paper that can obtain printing dots with excellent print clarity at each dot when ultraviolet laser irradiation is performed. In addition, the object of the present invention is to provide a printed matter in which the irradiated area is changed in color by irradiating the ultraviolet laser printing paper, a method for producing the same, and an ink composition used in the production of the ultraviolet laser printing paper. Furthermore, the object of the present invention is to provide a processed product using the ultraviolet laser printing paper or the printed matter.

[0014] Solutions for solving problems

[0015] The present inventors have discovered that in ultraviolet laser printing paper having a printed layer containing titanium oxide on a paper substrate, the above-mentioned problems can be solved by making the content of titanium oxide in the printed layer greater than a specific amount and the crystallite size of titanium oxide greater than a specific value, thereby completing the present invention.

[0016] The present invention relates to the following <1> ~ <16> .

[0017] <1> A paper for ultraviolet laser printing, comprising a printing layer containing titanium oxide on a paper substrate,

[0018] The content of titanium oxide in the printed layer is 0.1 g / m 2 above,

[0019] The crystallite size of titanium oxide in the printed layer is 30 nm or more.

[0020] <2> according to <1> The ultraviolet laser printing paper, wherein the crystallite size of the titanium oxide is less than 53nm.

[0021] <3> according to <1> or <2> The ultraviolet laser printing paper, wherein the titanium oxide in the printing layer is rutile titanium oxide, and the diffraction angle of the titanium oxide is less than 27.60°.

[0022] <4> according to <1> ~ <3> The ultraviolet laser printing paper described in any one of the preceding claims, wherein the length-weighted average fiber length of the pulp constituting the paper substrate is 2.0 mm or less.

[0023] <5> according to <1> ~ <4> The ultraviolet laser printing paper according to any one of the preceding claims, wherein the content of titanium oxide in the printing layer is 10 g / m 2 the following.

[0024] <6> according to <1> ~ <5> The ultraviolet laser printing paper as described in any one of the above, wherein the ratio of the number of fine fibers having a fiber length of 0.2 mm or less among the pulp fibers constituting the paper substrate is 4% or more and 40% or less.

[0025] <7> according to <1> ~ <6> The ultraviolet laser printing paper as described in any one of the above, wherein the water retention value of the pulp fibers constituting the paper substrate is 100% or more.

[0026] <8> according to <1> ~ <7> The ultraviolet laser printing paper described in any one of the above aspects has a sealing layer on the surface of the paper substrate opposite to the surface having the printing layer.

[0027] <9> according to <8> The ultraviolet laser printing paper also has a barrier layer.

[0028] <10> A printed matter consisting of <1> ~ <9> The ultraviolet laser printing paper described in any one of the above is obtained, wherein

[0029] The printed layer has a printed area containing discolored titanium oxide in at least a portion thereof,

[0030] The ratio of the Raman intensity derived from titanium oxide in the printed area to the Raman intensity derived from titanium oxide in the non-printed area is 0.70 or less.

[0031] <11> A processed product, which is <1> ~ <9> Any one of the ultraviolet laser printing paper or use <8> The printed matter.

[0032] <12> A method for producing a printed matter, comprising the following steps:

[0033] right <1> ~ <9> The ultraviolet laser printing paper described in any one of the above is irradiated with ultraviolet laser light to change the color of the irradiated area, thereby performing printing.

[0034] <13> according to <12> In the method for producing a printed article, the printing step is a step of irradiating ultraviolet laser light in such a way that the ratio of the Raman intensity of titanium oxide in the printing area to the Raman intensity of titanium oxide in the non-printing area becomes 0.70 or less.

[0035] <14> An ink composition for forming a printed layer that changes color when irradiated with ultraviolet laser, the printed layer containing titanium oxide having a crystallite size of 30 nm or more.

[0036] <15> according to <14> In the ink composition, the crystallite size of the titanium oxide is 53 nm or less.

[0037] <16> according to <14> or <15> In the ink composition, the titanium oxide is rutile titanium oxide, and the diffraction angle of the titanium oxide is less than 27.60°.

[0038] Effects of the Invention

[0039] According to the present invention, there is provided: ultraviolet laser printing paper that can obtain printing dots with excellent print clarity at each dot when ultraviolet laser irradiation is performed. In addition, according to the present invention, there are provided: a printed matter in which the irradiated area is changed in color by irradiating the ultraviolet laser printing paper, a method for producing the same, and an ink composition used in the production of the ultraviolet laser printing paper. Furthermore, according to the present invention, there is provided: a processed product made by using the ultraviolet laser printing paper or the printed matter. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a conceptual perspective view of an example of a liquid container having a printed area.

[0041] Figure 2A This is a photograph showing the depth composite image of the printed matter of Examples 1-4. Figure 2B This is a photograph showing a depth composite image of the printed matter of Comparative Example 1-2. DETAILED DESCRIPTION

[0042] [Paper for UV laser printing]

[0043] The ultraviolet laser printing paper of the present invention (hereinafter also referred to as "printing paper") comprises a printing layer containing titanium oxide on a paper substrate, wherein the content of the titanium oxide in the printing layer is 0.1 g / m 2 As described above, the crystallite size of titanium oxide in the printed layer is 30 nm or more.

[0044] According to the present invention, there is provided an ultraviolet laser printing paper which can obtain printed dots with excellent print clarity per dot when irradiated with ultraviolet laser.

[0045] The detailed reasons for achieving the above-mentioned effectiveness are not clear, but some of them are considered as follows.

[0046] By having a printing layer containing titanium oxide on a paper substrate, the titanium oxide in the printing layer changes color by laser irradiation based on ultraviolet laser, and printing can be performed. The color change of the titanium oxide is considered to be as follows: the ionic valence of the titanium oxide contained in the printing layer changes from tetravalent to trivalent, generating oxygen defects, thereby changing from white to black, thereby enabling visualization. It is believed that the ionic valence of titanium oxide changes when irradiated with light energy equivalent to the band gap of titanium oxide. The band gap of titanium oxide varies depending on the crystal system, but is generally around 3.0 to 3.2 eV, and the wavelength of light corresponding thereto is 420 nm or less. Therefore, even if a laser with a wavelength exceeding 420 nm (e.g., 532 nm, 1064 nm, 10600 nm) is used, it is not easy to implement printing caused by the change in the ionic valence of titanium oxide as in the present invention. At this time, by making the content of titanium oxide in the printing layer 0.1 g / m 2 As described above, a printed material having excellent visibility and excellent clarity of each printed dot can be obtained.

[0047] It is also believed that if the crystallite size of titanium oxide is 30 nm or more, crystal defects are reduced, the recombination of excited electrons and holes is suppressed, titanium oxide is easily reduced, and color change occurs easily, thereby obtaining print dots with excellent print clarity per dot.

[0048] It should be noted that, in this embodiment, the printable area refers to the area (portion) where the titanium oxide in the portion irradiated by the ultraviolet laser changes from white to black, and thus printing based on the irradiation of the ultraviolet laser can be performed, and the printing area refers to the portion of the printable area where the titanium oxide actually changes color and becomes visible due to the irradiation of the ultraviolet laser, that is, the portion irradiated by the ultraviolet laser. In addition, the non-printing area refers to the area (portion) in the printable area that is not irradiated with the ultraviolet laser.

[0049] Hereinafter, the present invention will be described in further detail.

[0050] The ultraviolet laser printing paper has a printable area containing titanium oxide.

[0051] The printing paper has a printing layer containing titanium oxide on a paper substrate. It should be noted that the printing layer only needs to be formed on one side of the paper substrate, or on both sides, but preferably the printing paper has a printing layer only on one side. In addition, the printing layer may be formed on the entire surface of the printing paper, or may be formed on a portion (part) where printing is desired.

[0052] In addition, in this embodiment, in order to improve the water resistance of the printing paper and to function as a protective layer for the printed layer, a resin layer may be further provided on the printed layer on the surface of the paper substrate where the printed layer is provided.

[0053] In addition, a sealing layer (heat seal layer) may be provided on the opposite side of the paper substrate to the surface provided with the printing layer. By providing the sealing layer, a printing paper having heat sealability can be formed.

[0054] Furthermore, the paper substrate may have a barrier layer mainly to prevent oxygen from penetrating. Preferably, the paper substrate has a barrier layer on the side opposite to the side having the printed layer, and when the paper substrate has a sealing layer on the side opposite to the side having the printed layer, preferably, the barrier layer is provided between the sealing layer and the paper substrate.

[0055] It should be noted that the printing paper of the present embodiment may have, for example, a plurality of printing layers, one layer or multiple layers as described above, and may have layers other than the above layers, for example, a bonding layer or an adhesive layer.

[0056] <Printing layer>

[0057] The ultraviolet laser printing paper of the present embodiment has a printing layer containing titanium oxide on a paper substrate. The printing layer can be provided by coating, and can also be provided by lamination, without particular limitation. That is, the printing layer is preferably a coating layer containing titanium oxide, or a laminated layer containing titanium oxide. In the present invention, from the viewpoint of being easy to provide the printing layer only in the desired position, and from the viewpoint of ease of manufacture, the printing layer is more preferably provided by coating. It should be noted that the aforementioned "provided by coating" means that the printing layer is formed by a coating liquid (ink composition), for example, including the case where it is formed by gravure printing, inkjet printing, etc.

[0058] The printed layer contains titanium oxide, and the content of titanium oxide in the printed layer is 0.1 g / m 2 above.

[0059] From the viewpoint of obtaining sufficient printing density, the content of titanium oxide in the printed layer is 0.1 g / m 2 Above, preferably 0.2g / m 2 More preferably 0.3 g / m 2 More preferably 0.4 g / m 2 In view of obtaining printing dots with excellent print clarity per dot, maximizing the printing density, suppressing the cost increase caused by containing more than the required amount of titanium oxide, and suppressing the amount of dust generated during ultraviolet laser irradiation (during printing), 10 g / m 2 Below, more preferably 7.5g / m 2 Below, more preferably 5g / m2 Below, more preferably 3.5g / m 2 the following.

[0060] If the content of titanium oxide in the printed layer is too high, there is a tendency to cause dust generation due to the scattering of titanium oxide when irradiated with ultraviolet laser. In addition, as a result of the generation of dust, the discolored titanium oxide is separated from the printed layer, and thus the clarity of printing per point tends to deteriorate.

[0061] It should be noted that as long as at least the printable area of ​​the ultraviolet laser printing paper contains titanium oxide in the above-mentioned content, the portion without a printing layer may exist in the non-printed area, and the portion with a titanium oxide content of less than 0.1 g / m2 may also exist. 2 From the viewpoint of ease of manufacture, it is also preferred to provide a titanium oxide content of 0.1 g / m2 over the entire area of ​​the printing paper. 2 The above printing layer.

[0062] In this embodiment, the printing paper may have an undercoat layer that does not contain titanium oxide, and a titanium oxide content of less than 0.1 g / m 2 The primer layer is used as the lower layer of the printed layer containing titanium oxide. In this case, the content of titanium oxide in all layers of the printed layer including the lower layer is 0.1 g / m 2 above.

[0063] In addition, when a resin layer described later is present on the printed layer, the resin layer does not belong to the printed layer.

[0064] From the perspective of print density, print clarity per dot, and suppression of dust generation during ultraviolet laser irradiation, the print layer should be 2 The mass (solid content, basis weight) is preferably 1.0 g / m 2 More preferably 2.5 g / m 2 More preferably 4.5 g / m 2 More than, and preferably 50g / m 2 Below, more preferably 40g / m 2 Below, more preferably 30g / m 2 the following.

[0065] The content of titanium oxide in the printed layer (solid component) is preferably 0.3 mass % or more, more preferably 1.0 mass % or more, further preferably 2.0 mass % or more, and further preferably 2.5 mass % or more, from the viewpoint of printing concentration and print clarity of each point. Furthermore, from the viewpoint of maximizing the printing concentration, suppressing the cost increase caused by containing titanium oxide more than required, from the viewpoint of ease of forming the printed layer, and suppressing dust generation during ultraviolet laser irradiation, it is preferably 95 mass % or less, more preferably 85 mass % or less, further preferably 75 mass % or less, and further preferably 60 mass % or less.

[0066] The thickness of the printed layer is preferably 0.3 μm or more, more preferably 0.5 μm or more, further preferably 1.0 μm or more, and further preferably 2.0 μm or more, from the viewpoint of print clarity per point and ease of forming the printed layer, and is preferably 40.0 μm or less, more preferably 30.0 μm or less, further preferably 25.0 μm or less, and further preferably 20.0 μm or less, from the viewpoint of maximizing the printing concentration and ease of forming the printed layer.

[0067] The thickness of the printed layer was measured from an electron microscope (SEM) observation image of a cross section of the printing paper.

[0068] The substrate of the printing paper is a paper substrate as described below, and the paper substrate itself may contain titanium oxide. When the paper substrate contains titanium oxide, a clearer image tends to be obtained. In particular, when the thickness of the printing layer is thin, when the paper substrate itself contains titanium oxide, a clearer image tends to be obtained. In this case, when the thickness of the printing layer is 2.0 μm or less, the effect tends to become more obvious when the paper substrate contains titanium oxide.

[0069] When the paper base material contains titanium oxide, the content of titanium oxide in the paper base material is preferably 5 mass % or more, more preferably 10 mass % or more, further preferably 15 mass % or more, and further preferably 20 mass % or more.

[0070] The printed layer preferably contains a thermoplastic resin in addition to titanium oxide. Furthermore, it may contain an inorganic pigment other than titanium oxide. Each component is described in detail below.

[0071] (Titanium Oxide)

[0072] The titanium oxide contained in the printed layer is represented by the composition formula TiO2, also known as titanium dioxide or Titania.

[0073] In this embodiment, the crystallite size of titanium oxide in the printed layer is 30 nm or more. If the crystallite size of titanium oxide in the printed layer is less than 30 nm, there are many crystal defects, and the recombination of excited electrons and holes excited by ultraviolet laser irradiation is likely to occur. As a result, titanium oxide is not easily reduced, and the print clarity of each point is poor. The crystallite size of titanium oxide is preferably 35 nm or more, and more preferably 40 nm or more.

[0074] In addition, the upper limit of the crystallite size of titanium oxide is not particularly limited, but from the viewpoint of dispersion stability in the coating liquid and the printed layer, it is preferably 60 nm or less, more preferably 56 nm or less, and further preferably 53 nm or less. If the upper limit of the crystallite size of titanium oxide is within the above range, the dispersion stability of titanium oxide in the coating liquid and the printed layer is good, and the printing uniformity is improved, so it is preferred.

[0075] The crystallite size of titanium oxide is measured according to the method described in Examples.

[0076] It should be noted that the crystallite size was calculated based on the Scherrer equation, and as the Bragg angle, in the case of anatase titanium oxide, the measured value of the maximum intensity derived from the 101 plane was used, and in the case of rutile titanium oxide, the measured value of the maximum intensity derived from the 110 plane was used.

[0077] The titanium oxide may be of any crystal structure, and is preferably at least one selected from rutile titanium oxide, anatase titanium oxide and brookite titanium oxide. From the viewpoint of availability and stability, it is more preferably at least one selected from rutile titanium oxide and anatase titanium oxide, and rutile titanium oxide is further preferred.

[0078] The crystal form of titanium oxide can be determined by a known method, specifically, by analysis of Raman spectroscopy, XRD spectra, etc. For example, in the case of identification by Raman spectroscopy, generally, in the rutile type, the crystal form of titanium oxide is 447±10 cm -1 、609±10cm -1 A peak was confirmed at 395±10cm in anatase type. -1 、516±10cm -1 、637±10cm -1 The peak was confirmed.

[0079] The titanium oxide may be used alone or in combination of two or more.

[0080] When the titanium oxide is rutile titanium oxide, the diffraction angle of the titanium oxide is preferably 27.60° or less from the viewpoint of the print clarity of each point. The Bragg angle of rutile titanium oxide is originally around 27.40° (depending on the literature, for example, 27.44°), but if the crystallinity is low, the diffraction angle tends to be higher. If the diffraction angle of titanium oxide exceeds 27.60°, the crystallinity is low and the discoloration is suppressed, so there is a tendency for the print clarity of each point to be poor.

[0081] When the titanium oxide is rutile titanium oxide, the diffraction angle of the titanium oxide is preferably 27.60° or less, more preferably 27.55° or less, and further preferably 27.50° or less.

[0082] In the case of the rutile type, as described above, the diffraction angle of titanium oxide is an actually measured value of the maximum intensity derived from the 110 plane.

[0083] The shape of titanium oxide is not particularly limited, and may be any shape such as amorphous, spherical, rod-like, or needle-like.

[0084] When the titanium oxide is amorphous or spherical, the average particle size of the titanium oxide is not particularly limited. From the viewpoint of excellent print clarity at each point and the viewpoint of obtaining printing paper with excellent surface smoothness, it is preferably 0.01 μm or more, more preferably 0.05 μm or more, further preferably 0.1 μm or more, further preferably more than 0.15 μm, particularly preferably 0.16 μm or more, and preferably 20.0 μm or less, more preferably 5.0 μm or less, further preferably 1.5 μm or less, further preferably 0.50 μm or less.

[0085] In addition, when the titanium oxide is needle-shaped, the long diameter of the titanium oxide is not particularly limited. From the perspective of excellent print clarity per point and the perspective of obtaining printing paper with excellent surface smoothness, it is preferably 0.1 μm or more, more preferably 0.5 μm or more, and further preferably 1.5 μm or more, and preferably 50.0 μm or less, more preferably 30.0 μm or less, and further preferably 15.0 μm or less. In addition, the short diameter is preferably 0.01 μm or more, more preferably 0.03 μm or more, and further preferably 0.05 μm or more, and preferably 3.0 μm or less, more preferably 1.5 μm or less, and further preferably 1.0 μm or less. In addition, when the titanium oxide is needle-shaped, the aspect ratio (long diameter / short diameter) is preferably 5 or more, more preferably 10 or more, and further preferably 15 or more, and preferably 300 or less, more preferably 100 or less, and further preferably 30 or less.

[0086] The average particle size, major diameter and minor diameter of titanium oxide are measured according to the method described in the examples. It should be noted that the particle size, major diameter and minor diameter values ​​of titanium oxide used as a raw material can be used, and the catalog values ​​of the particle size, major diameter and minor diameter of titanium oxide used as a raw material can also be used.

[0087] (Thermoplastic resin)

[0088] The thermoplastic resin used in the printing layer functions as a binder.

[0089] The thermoplastic resin used as the printing layer is not particularly limited. When the printing layer is provided by coating, it can be applied in the form of an aqueous coating liquid or in the form of an organic solvent-based coating liquid (oil-based coating liquid). It should be noted that when the printing layer is provided by coating, the printing layer is also referred to as a coating layer. In addition, the composition used to provide the coating layer is also referred to as a coating liquid or an ink composition.

[0090] When the thermoplastic resin is applied in the form of an aqueous coating liquid, it is preferable that the thermoplastic resin is a water-dilutable thermoplastic resin. Examples of the water-dilutable resin include water-soluble, emulsion-type, and dispersion-type resins.

[0091] The water-dilutable thermoplastic resin may be a natural resin or a synthetic resin, for example, starch derivatives, casein, shellac, polyvinyl alcohol and its derivatives, acrylic resins, maleic acid resins, polyurethane resins, polyester resins, styrene-butadiene resins, vinyl chloride resins, and polyolefin resins.

[0092] More specifically, examples of acrylic resins include acrylic resins obtained by copolymerizing (meth)acrylic acid with its alkyl ester or styrene as monomer components, styrene-maleic acid resins, styrene-acrylic acid-maleic acid resins, olefin-(meth)acrylic acid copolymer resins (e.g., ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers), and the like.

[0093] Among these, from the viewpoint of the stability of the coating liquid and the solvent resistance of the printed layer, it is preferably at least one selected from the group consisting of starch derivatives, casein, shellac, polyvinyl alcohol and its derivatives, acrylic resins, maleic acid resins and styrene-butadiene resins, more preferably at least one selected from the group consisting of starch derivatives, polyvinyl alcohol, polyvinyl alcohol derivatives, acrylic resins, maleic acid resins and styrene-butadiene resins, further preferably at least one selected from the group consisting of starch derivatives, polyvinyl alcohol, polyvinyl alcohol derivatives, acrylic resins and styrene-butadiene resins, and still further preferably at least one selected from the group consisting of polyvinyl alcohol, polyvinyl alcohol derivatives, acrylic resins and styrene-butadiene resins.

[0094] These resins may be used alone or in combination of two or more.

[0095] When forming an organic solvent-based coating liquid (oily coating liquid), it is preferred to use a known thermoplastic resin such as a cellulose resin (e.g., nitrocellulose, cellulose acetate, cellulose acetate propionate), a polyurethane resin, an acrylic resin, or a vinyl chloride copolymer resin.

[0096] The content of the thermoplastic resin is not particularly limited and can be appropriately selected according to the type of thermoplastic resin, the content of titanium oxide in the coating liquid, the content of the inorganic pigment described later, etc. For example, it is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 15% by mass or more in the solid content of the coating liquid, and is preferably 99% by mass or less, and more preferably 98% by mass or less.

[0097] When the printed layer is provided by coating, the coating layer is preferably provided by applying and drying a coating liquid.

[0098] The coating liquid is preferably an aqueous coating liquid, and examples of the aqueous medium used include water or a mixture of water and a water-miscible solvent.

[0099] As the water-miscible solvent, lower alcohols, polyols and their alkyl ethers or alkyl esters can be mentioned. Specifically, lower alcohols such as methanol, ethanol, n-propanol, isopropanol, polyols such as ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, glycerol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monoacetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monoacetate, diethylene glycol monomethyl ether, dipropylene glycol monomethyl ether, etc. can be mentioned.

[0100] In the case of an organic solvent-based coating liquid, examples include known solvents such as aromatic organic solvents such as toluene and xylene, ethyl acetate, n-propyl acetate, isobutyl acetate, ester-based organic solvents, ketone-based organic solvents such as methyl ethyl ketone and methyl isobutyl ketone, alcohol-based organic solvents such as methanol, ethanol, isopropanol, and n-butanol, and hydrocarbon-based solvents such as methylcyclohexane.

[0101] The solid content concentration of the coating liquid is not particularly limited, but is preferably 10% by mass or more, more preferably 20% by mass or more, further preferably 30% by mass or more, and preferably 80% by mass or less, more preferably 75% by mass or less, further preferably 70% by mass or less, and further preferably 65% ​​by mass or less, from the viewpoint of obtaining the desired coating layer thickness, making the coating liquid form a viscosity that is easy to apply, and the viewpoint of ease of drying.

[0102] The viscosity of the coating liquid is preferably 10 mPa·s (20°C) or more, more preferably 15 mPa·s (20°C) or more, further preferably 20 mPa·s (20°C) or more, based on measurement with a Brookfield viscometer, from the viewpoint of obtaining coating suitability, the desired thickness of the coating layer, and ease of drying. Furthermore, it is preferably 5000 mPa·s (20°C) or less, more preferably 4000 mPa·s (20°C) or less, further preferably 3000 mPa·s (20°C) or less, and further preferably 2000 mPa·s (20°C) or less.

[0103] When the printed layer is provided by lamination, it is preferred that a thin film containing titanium oxide is laminated on the substrate. In addition, when the printed layer is provided by lamination, the printed layer is also referred to as a laminate layer.

[0104] The thermoplastic resin constituting the laminate layer is not particularly limited, and any thermoplastic resin can be appropriately selected from known thermoplastic resins as long as it can encapsulate titanium oxide and be processed into a film. Specifically, polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, polyolefin resins such as polyvinyl chloride, polyvinylidene chloride, polybutene, polybutadiene, ethylene-vinyl acetate copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, and polymethylpentene; polycarbonate; polyurethane; polyamide; polyacrylonitrile; poly(meth)acrylate, etc. are exemplified.

[0105] Among these, the resin constituting the laminated layer preferably includes polyolefins such as polyethylene, polypropylene, and ethylene-propylene copolymers, polyesters such as polyethylene terephthalate, polybutylene terephthalate, polylactic acid, and polybutylene succinate, from the viewpoint that it can be used universally, has a high transmittance of ultraviolet rays, and can discolor titanium oxide to the inside of the film. It is more preferable to include at least one selected from the group consisting of polyethylene, polypropylene, ethylene-propylene copolymers, polyethylene terephthalate, polylactic acid, and polybutylene succinate, and it is further preferable to include at least one selected from the group consisting of polyethylene, polypropylene, ethylene-propylene copolymers, polyethylene terephthalate, polylactic acid, and polybutylene succinate. The resin constituting the laminated layer is further preferably a polyolefin, and further preferably at least one selected from the group consisting of polyethylene and polypropylene. Polyethylene (PE) is roughly classified into linear low-density polyethylene (LLDPE), low-density polyethylene (LDPE), medium-density polyethylene (MDPE), and high-density polyethylene (HDPE). Among these, low density polyethylene (LDPE) is preferred because of its excellent extrusion lamination properties.

[0106] In addition, it is preferable to use a polyester which is a biodegradable resin as the resin constituting the lamination layer in terms of reducing the environmental load, and examples thereof include polylactic acid and polybutylene succinate.

[0107] These resins may be used alone or in combination of two or more.

[0108] From the viewpoint of suppressing dust generation during ultraviolet laser irradiation, the content of thermoplastic resin in the laminate layer is preferably 20 mass % or more, more preferably 30 mass % or more, further preferably 50 mass % or more, further preferably 70 mass % or more, particularly preferably 80 mass % or more, and is preferably 99 mass % or less, more preferably 98 mass % or less, further preferably 95 mass % or less.

[0109] (Inorganic pigments other than titanium oxide)

[0110] The printing layer may contain other components in addition to the titanium oxide and the thermoplastic resin. As other components, inorganic pigments other than titanium oxide (hereinafter also referred to as "inorganic pigments") may be cited. By containing inorganic pigments other than titanium oxide, the scattering of titanium oxide is suppressed, the generation of dust during ultraviolet laser irradiation is suppressed, and the result is that the print clarity per point is improved, so it is preferred.

[0111] Examples of the inorganic pigment include calcium carbonate, talc, silica, kaolin, magnesium oxide, mica, aluminum hydroxide, and barium sulfate. Among these, at least one selected from the group consisting of calcium carbonate, talc, silica, kaolin, magnesium oxide, zinc oxide, and mica is preferred, and at least one selected from the group consisting of calcium carbonate and talc is more preferred.

[0112] The inorganic pigment may be used alone or in combination of two or more.

[0113] The shape of the inorganic pigment is not particularly limited, and may be any shape such as amorphous, spherical, plate-like, rod-like, or needle-like.

[0114] When the inorganic pigment is amorphous, spherical or plate-shaped, the average particle size of the inorganic pigment is not particularly limited, but from the viewpoint of obtaining printing paper with excellent surface smoothness and the viewpoint of suppressing dust generation, it is preferably 0.1 μm or more, more preferably 0.15 μm or more, further preferably 0.20 μm or more, and preferably 10 μm or less, more preferably 5 μm or less, further preferably 3 μm or less.

[0115] In addition, when the inorganic pigment is needle-shaped, the major diameter of the inorganic pigment is not particularly limited. From the perspective of obtaining printing paper with excellent surface smoothness and suppressing dust generation, it is preferably 0.5 μm or more, more preferably 1.0 μm or more, and further preferably 2.0 μm or more, and preferably 100 μm or less, more preferably 10 μm or less, and further preferably 5 μm or less. In addition, the minor diameter is preferably 0.1 μm or more, more preferably 0.5 μm or more, and further preferably 1.0 μm or more, and preferably 50 μm or less, more preferably 10 μm or less, and further preferably 1.0 μm or less. In addition, when the inorganic particles are needle-shaped, the aspect ratio (major diameter / minor diameter) is preferably 1.5 or more, more preferably 2.0 or more, and further preferably 3.0 or more, and preferably 100 or less, more preferably 50 or less, and further preferably 30 or less.

[0116] When the printed layer contains an inorganic pigment other than titanium oxide, the content of the inorganic pigment in the printed layer is preferably 2 mass % or more, more preferably 10 mass % or more, further preferably 20 mass % or more, further preferably 30 mass % or more, particularly preferably 50 mass % or more, and is preferably 95 mass % or less, more preferably 90 mass % or less, further preferably 85 mass % or less, further preferably 80 mass % or less, from the viewpoint of improving the print clarity of each point and suppressing dust generation during ultraviolet laser irradiation.

[0117] When the printed layer contains an inorganic pigment other than titanium oxide, the mass ratio of titanium oxide to the inorganic pigment other than titanium oxide (titanium oxide / inorganic pigment other than titanium oxide) is preferably 0.01 or more, more preferably 0.03 or more, further preferably 0.10 or more, and is preferably 4.0 or less, more preferably 2.0 or less, further preferably 1.0 or less, from the viewpoint of improving the print clarity of each point and suppressing dust generation during ultraviolet laser irradiation.

[0118] The printing layer may contain, in addition to the above-mentioned components, a film-forming agent, a pigment dispersant, a pigment dispersing resin, an anti-blocking agent, a wetting agent, a viscosity regulator, a pH regulator, a defoaming agent, a general surfactant, and the like.

[0119] (Coating liquid)

[0120] When the printed layer is provided by coating, when the coating liquid (ink composition) is an aqueous coating liquid, it is preferably obtained by mixing the above-mentioned various materials with an aqueous medium. It should be noted that before mixing with the aqueous medium, titanium oxide, thermoplastic resin, water, and inorganic pigments other than titanium oxide as required, water-miscible solvents, pigment dispersants, pigment dispersible resins, etc. can be mixed and kneaded, and water, water-miscible solvents as required, and the remainder of the prescribed materials can be further added and mixed.

[0121] In addition, when the coating liquid is an oily coating liquid, titanium oxide or pigments other than titanium oxide may be added after mixing the organic solvent with the resin, or a pigment dispersant, pigment dispersible resin, etc. may be pre-added to the mixed liquid of the organic material and the resin and then added.

[0122] The coating liquid is obtained by mixing and dispersing the above-mentioned components in a high-speed mixer such as a homomixer or a laboratory blender, or a disperser such as a Cowles disperser, a three-roll mill, or a bead mill.

[0123] The coating liquid can be applied to the substrate by any method, including flexographic printing, inkjet printing, gravure printing, screen printing, pad printing, spraying, Meyer rod, gravure coater, air knife coater, blade coater, rod coater, die coater, bar coater, etc.

[0124] 〔Lamination layer〕

[0125] When the printed layer is a laminated layer, the laminated film is obtained by preparing a raw material composition in which at least titanium oxide and a thermoplastic resin and, if necessary, inorganic pigments and other materials are melt-kneaded, forming the composition into a film, and then stretching the composition as needed.

[0126] In addition, when preparing the raw material composition, a masterbatch containing titanium oxide and an inorganic pigment at a high concentration may be prepared and then mixed with the resin.

[0127] In addition, the materials uniformly mixed in advance may be charged into the molding machine, or may be mixed in a hopper or a kneading machine integrated with the molding machine.

[0128] The method for forming into a film may be appropriately selected from conventionally known methods, and for example, may be appropriately selected from melt extrusion, melt casting, calendaring, and the like.

[0129] Preferably, the substrate and the film may be attached or laminated via an adhesive layer.

[0130] In addition, as an adhesive layer, it does not specifically limit, What is necessary is just to select suitably from well-known adhesive layers and use. Specific example is the adhesive layer of Unexamined-Japanese-Patent No. 2012-57112.

[0131] Specific examples of the lamination process include laminating a paper base material and a laminating layer by heat lamination, dry lamination, wet lamination, extrusion lamination, and the like.

[0132] Among these, the extrusion lamination method is preferred from the viewpoint of eliminating the need for a step of laminating a lamination layer and a paper substrate and a production step.

[0133] <Paper base material>

[0134] In this embodiment, a paper substrate is used as the substrate.

[0135] As the raw material pulp constituting the paper substrate, for example, wood pulp, non-wood pulp and deinked pulp can be mentioned. As the wood pulp, there is no particular limitation, and for example, chemical pulps such as hardwood bleached kraft pulp (LBKP), hardwood unbleached kraft pulp (LUKP), softwood bleached kraft pulp (NBKP), softwood unbleached kraft pulp (NUKP), sulfite pulp (SP), dissolving pulp (DP), alkaline pulp (AP), oxygen bleached kraft pulp (OKP), semi-chemical pulp (SCP), chemical groundwood pulp (CGP) and other semi-chemical pulps, groundwood pulp (GP), thermomechanical pulp (TMP), chemical thermomechanical pulp (CTMP) and other mechanical pulps can be mentioned. As the non-wood pulp, there is no particular limitation, and for example, cotton pulps such as cotton lint and lint, and non-wood pulps such as hemp, straw, bamboo, and bagasse can be mentioned. The deinked pulp is not particularly limited, and examples thereof include deinked pulp made from waste paper. The raw material pulp may be one of the above-mentioned pulps alone, or two or more of the above-mentioned pulps may be mixed. It should be noted that the raw material pulp may be mixed with organic synthetic fibers such as polyamide fibers and polyester fibers, recycled fibers such as polynosic fibers, and inorganic fibers such as glass fibers, ceramic fibers, and carbon fibers.

[0136] As for the raw material pulp, wood pulp and deinked pulp are preferred from the viewpoint of easy availability. In addition, among wood pulps, the raw material pulp is preferably chemical pulp from the viewpoint of uniformity of texture, more preferably kraft pulp, further preferably at least one selected from hardwood kraft pulp such as eucalyptus and acacia, and softwood kraft pulp such as pine and cedar, further preferably at least one selected from hardwood bleached kraft pulp (LBKP) and softwood bleached kraft pulp (NBKP), and particularly preferably LBKP.

[0137] The length-weighted average fiber length of the pulp constituting the paper substrate is preferably 0.6 mm or more, more preferably 0.65 mm or more, further preferably 0.7 mm or more, and is preferably 3.5 mm or less, more preferably 2.5 mm or less, further preferably 2.0 mm or less, further preferably 1.5 mm or less, and particularly preferably 1.0 mm or less, from the viewpoint of suppressing coating unevenness and improving print clarity.

[0138] If the length-weighted average fiber length of the pulp constituting the paper substrate is below the above upper limit, the pulps are densely entangled with each other, thereby reducing the porosity of the paper substrate. When a coating layer is provided, coating unevenness is suppressed, the print clarity of each point is excellent, and a printed material with excellent printing uniformity is obtained, which is preferred.

[0139] When the length-weighted average fiber length of the pulp constituting the paper base is not less than the above lower limit, the strength of the paper base is improved and paper dust is reduced, so that it is also possible to suppress the fall-off of the printed part, which is preferred.

[0140] The length-weighted average fiber length of the pulp constituting the paper substrate was measured according to the method described in Examples.

[0141] The average fiber width of the pulp fibers constituting the paper substrate is preferably 14.0 μm or more, more preferably 15.0 μm or more, further preferably 15.5 μm or more, further preferably 16.0 μm or more, and is preferably 35.0 μm or less, preferably 33.0 μm or less, more preferably 31.0 μm or less, further preferably 28.0 μm or less, further preferably 24.0 μm or less, further preferably 21.0 μm or less.

[0142] If the average fiber width of the pulp fibers constituting the paper substrate is 35.0 μm or less, the pulps are densely entangled with each other, thereby smoothing the surface of the paper substrate, suppressing uneven coating when a printing layer is provided, and smoothing the surface of the printing layer, thereby achieving excellent print clarity at each point and obtaining a printed product with excellent print uniformity, which is preferred. In addition, if the average fiber width is 14.0 μm or more, the strength of the paper substrate is improved, and further, paper dust is reduced, so that the fall-off of the printed part can also be suppressed, which is preferred.

[0143] The average fiber width of pulp fibers constituting the paper substrate can be measured by the method described in Examples.

[0144] The ratio of the number of fine fibers with a fiber length of less than 0.2 mm in the pulp constituting the paper substrate is preferably 4% or more, more preferably 5% or more, further preferably 6% or more, further preferably 10% or more, particularly preferably 15% or more, and preferably 40% or less, more preferably 30% or less, further preferably 20% or less.

[0145] If the ratio of the number of fine fibers is 40% or less, the strength of the paper substrate can be ensured, and the paper dust generated by the detachment of the fine fibers is suppressed, resulting in excellent printing uniformity, which is preferred. In addition, if the ratio of the number of fine fibers is 4% or more, the fine fibers are arranged in a form of filling the gaps between the fibers, the pores of the paper substrate are reduced, and when a coating layer is provided, uneven coating is suppressed, resulting in improved printing uniformity, which is preferred.

[0146] The number ratio of fine fibers having a fiber length of 0.2 mm or less in the pulp constituting the paper substrate is calculated as follows: the paper substrate is disintegrated by the method described in the Examples, and the fiber length of the obtained pulp slurry is measured using a fiber length measuring device (e.g., Valmet, Model FS-5, with UHD base unit) to calculate the ratio. Fibers having a fiber length of 0.2 mm or less and a fiber width of 75 μm or less are formed into fine fibers, and the number ratio of the fine fibers relative to the measured number of pulp is calculated.

[0147] The water retention value of the pulp fibers constituting the paper substrate is preferably 100% or more, more preferably 105% or more, further preferably 110% or more, and further preferably 115% or more, from the viewpoint of suppressing dust generation caused by ultraviolet laser printing. The upper limit is not particularly limited, but from the viewpoint of ease of manufacturing, it is preferably 200% or less, more preferably 170% or less, and further preferably 150% or less.

[0148] It is believed that the titanium oxide that absorbs the light of the ultraviolet laser releases heat, thereby generating dust generated by the scattering of the titanium oxide. It is believed that by setting the water retention value of the pulp constituting the paper base material located directly below the printing layer to 100% or more, the amount of water in the paper base material increases, and the heat generated by the titanium oxide escapes as vaporization heat, so that the scattering of the titanium oxide is suppressed and the dust generation is suppressed.

[0149] If the hemicellulose content in pulp fibers is high, the water retention value of the pulp fibers tends to be high. Therefore, when dissolving pulp having a high α-cellulose content and a reduced hemicellulose content is used as raw material pulp, the water retention value tends to decrease.

[0150] In addition, the higher the beating degree of pulp fibers, the better the water retention value tends to be. Therefore, from the viewpoint of water retention value, it is preferred to use pulp fibers having a low Canadian Standard freeness (CSF) and a high beating degree.

[0151] The water retention value of the pulp fibers constituting the paper substrate was measured according to the method described in Examples.

[0152] From the viewpoint of obtaining the desired fiber width and fiber length, the ratio of the number of fine fibers and the water retention value, the Canadian standard freeness (CSF) of the wood pulp used in the paper substrate is preferably 150 mL or more, more preferably 300 mL or more, further preferably 400 mL or more, and preferably 800 mL or less, more preferably 750 mL or less, further preferably 700 mL or less, and further preferably 600 mL or less.

[0153] Here, CSF is Canadian standard freeness based on JIS P 8121-2:2012.

[0154] The paper base material is obtained by making paper from a pulp slurry to which an internal additive is added as necessary.

[0155] In addition to the above-mentioned pulp, the paper base material may contain fillers, sizing agents, drying enhancers, paper wet strength agents (e.g., polyamide polyamine epichlorohydrin), yield improvers (e.g., aluminum sulfate), filterability improvers, pH adjusters, softeners, antistatic agents, defoamers, dyes / pigments, and other known internal additives for papermaking, as needed.

[0156] Examples of the filler include kaolin, talc, titanium oxide, heavy calcium carbonate, light calcium carbonate, calcium sulfite, gypsum, calcined kaolin, white carbon, amorphous silica, delaminated kaolin, diatomaceous earth, magnesium carbonate, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, and zinc hydroxide.

[0157] Examples of the sizing agent include rosin-based, alkyl ketene dimer-based, alkenyl succinic anhydride-based, styrene-acrylic, higher fatty acid-based, and petroleum resin-based sizing agents.

[0158] In papermaking of the paper substrate, a known wet papermaking machine, such as a fourdrinier papermaking machine, a gap-wire papermaking machine, a cylinder papermaking machine, a short-wire papermaking machine, etc., can be appropriately selected and used. Next, the paper layer formed by the papermaking machine is conveyed to a felt and dried in a dryer. A multi-stage drum dryer can also be used as a pre-dryer before drying in the dryer.

[0159] In addition, the paper substrate obtained as described above may be subjected to a surface treatment using a calender to achieve uniformity of thickness and profile and improve printability. For the calender treatment, a known calender treatment machine may be appropriately selected and used.

[0160] The paper substrate may be appropriately selected from conventionally known paper substrates such as liner paper, kraft paper, premium paper, and coated paper.

[0161] The paper substrate may be a single layer or a multi-layer structure, and may have a multi-layer structure having different pulp compositions.

[0162] The basis weight of the paper substrate is preferably 30 g / m2 from the viewpoint of improving the strength and printability of the printing paper. 2 More preferably 35g / m 2 More than, and preferably 1000g / m 2 Below, more preferably 700g / m 2 Below, more preferably 500g / m 2 the following.

[0163] The basis weight is measured by the method specified in JIS P 8124:2011.

[0164] The thickness of the paper substrate is not particularly limited, but from the viewpoint of improving the strength and printing suitability of printing paper, it is preferably 30 μm or more, more preferably 40 μm or more, and further preferably 50 μm or more, and is preferably 1200 μm or less, more preferably 850 μm or less, and further preferably 600 μm or less.

[0165] The thickness of the paper substrate can be measured by the method described in JIS P 8118:2014.

[0166] The density of the paper substrate is not particularly limited, but is preferably 0.3 g / cm 3 More preferably 0.5 g / cm 3 More preferably 0.7 g / cm 3 More than, and preferably 1.2g / cm 3 Less than, more preferably 1.0 g / cm 3 Below, more preferably 0.8 g / cm 3 the following.

[0167] The density of the paper substrate is calculated from the basis weight and thickness.

[0168] <Resin layer>

[0169] The printing paper of this embodiment may further include a resin layer on the printing layer in order to improve the water resistance of the printing paper and to function as a protective layer. Printing paper having a resin layer previously provided on the printing layer may be used.

[0170] The total light transmittance of the resin layer is preferably 40% or more, more preferably 60% or more, further preferably 70% or more, further preferably 80% or more, particularly preferably 90% or more, and is 100% or less. The upper limit is not particularly limited.

[0171] The total light transmittance is measured in accordance with JIS K 7361-1:1997.

[0172] The resin constituting the resin layer is not particularly limited as long as the total light transmittance is preferably 40% or more and can be provided on a sheet substrate. From the viewpoint of transparency and easy provision of the resin layer, when the resin layer and a paper substrate provided with a printed layer are adhered to each other via an adhesive layer or laminated by lamination, or when the resin layer provided with a printed layer and a paper substrate are adhered to each other via an adhesive layer, it is preferably at least one selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate, polyvinyl alcohol, polyamide and starch, more preferably at least one selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate and polyvinyl alcohol, further preferably polyethylene and polypropylene, and particularly preferably polyethylene.

[0173] In addition, when the resin layer is provided by coating, acrylic resin, styrene-maleic acid resin, water-soluble polyurethane resin, water-soluble polyester resin, etc. are exemplified.

[0174] Examples of acrylic resins include resins obtained by copolymerizing (meth)acrylic acid with its alkyl ester, styrene, unsaturated carboxylic acid other than (meth)acrylic acid, ethylene, propylene and other monomers. Specifically, examples include ethylene-(meth)acrylic acid copolymers and styrene-acrylic acid-maleic acid resins, and ethylene-(meth)acrylic acid copolymers are preferred.

[0175] The paper substrate having the resin layer and the print layer can be laminated by any method without particular limitation. From the viewpoint of ease of production, it is preferred that the paper substrate having the resin layer and the print layer be bonded together via an adhesive layer or laminated and a clear coating material be applied in the form of a liquid coating material. Alternatively, a print layer may be formed on the resin layer in advance and bonded to the paper substrate via an adhesive layer.

[0176] When the resin layer is provided locally, it is preferably pasted with an adhesive from the viewpoint of ease of production. In addition, when the resin layer is provided over a wide area, it is preferably laminated.

[0177] In addition, as an adhesive layer, it does not specifically limit, What is necessary is just to select suitably from well-known adhesive layers and use. Specific example is the adhesive layer of Unexamined-Japanese-Patent No. 2012-57112.

[0178] The thickness of the resin layer is not particularly limited, but from the perspective of obtaining clear prints and the operability of printed materials and printing paper, it is preferably 5 μm or more, more preferably 10 μm or more, and further preferably 15 μm or more, and is preferably 100 μm or less, more preferably 75 μm or less, and further preferably 50 μm or less.

[0179] <Sealing layer>

[0180] The printing paper of the present embodiment may have a sealing layer on the opposite side of the paper substrate to the side provided with the printing layer. The sealing layer is a layer that melts and adheres under heating, ultrasound, etc. The printing paper of the present embodiment may have a sealing layer on both sides of the paper substrate. In addition, from the viewpoint of imparting heat sealability, it is preferred that a sealing layer is provided on the topmost layer of at least one side, and more than two layers of sealing layers may be formed on one side. It should be noted that in the case of having a sealing layer, it is preferred that the sealing layer is provided on at least the opposite side of the side of the paper substrate provided with the printing layer, and it may also be provided on the side provided with the printing layer.

[0181] In addition, the sealant layer may be provided on the entire surface of the paper substrate opposite to the surface on which the printed layer is provided, or may be provided on a portion that requires heat sealability.

[0182] By providing a sealing layer on the opposite side of the paper substrate to the surface provided with the printing layer, heat sealability is imparted, and a printing paper having heat sealability is provided. Furthermore, it is preferred that the sealing layer also imparts gas barrier properties. Here, the gas barrier property mainly refers to the barrier property to at least one selected from oxygen and water vapor, and it may also have barrier properties to other gases. The printing paper of this embodiment also preferably has at least water vapor barrier properties, and further preferably has oxygen barrier properties.

[0183] The resin constituting the sealing layer (hereinafter also referred to as "sealing layer resin") is not particularly limited, and examples thereof include vinyl chloride resin, vinyl acetate resin, vinyl chloride-vinyl acetate copolymer, acrylic resin, polyester resin, olefin resin, styrene resin, styrene acrylic resin (e.g., styrene-acrylic acid copolymer), ethylene acrylic resin (ethylene-(meth)acrylic acid copolymer), and modified products thereof. The sealing layer resin may be used alone or in combination of two or more.

[0184] As the sealing layer resin, either a synthetic product or a commercial product may be used. As the commercial product, those described in Examples and the like may be used.

[0185] The sealing layer can be formed by melt extrusion, lamination with an adhesive, etc., and a method of forming the sealing layer by preparing a coating liquid for the sealing layer and applying the coating liquid is exemplified. As the adhesive, a known adhesive can be used. It should be noted that more than two layers of sealing layers can be formed. It should be noted that, for the sealing layer, when a resin film for laminating the sealing layer with an adhesive, etc. is used, the resin film can be unstretched or can be stretched uniaxially or biaxially.

[0186] When the sealing layer is formed by stacking, the resin for the sealing layer is preferably at least one selected from the group consisting of polyolefin resins, polyamide resins, polyester resins and polyvinylidene chloride resins, more preferably a polyolefin resin, and even more preferably a polyolefin resin, from the viewpoint of heat sealability and gas barrier properties.

[0187] When the sealant layer is a laminated sealant layer composed of two or more layers, the surface opposite to the paper base layer is preferably a polyolefin resin layer, and more preferably a polyethylene resin layer, from the viewpoint of heat sealability.

[0188] From the viewpoint of heat sealability and gas barrier properties, the polyolefin resin is more preferably at least one selected from the group consisting of polyethylene, polypropylene and ethylene-propylene copolymers, and further preferably at least one of polyethylene and polypropylene.

[0189] It should be noted that the polyethylene may be low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), or high-density polyethylene (HDPE).

[0190] Examples of the polyamide resin include nylon 6, nylon 11, nylon 12, nylon 66, nylon 610, and nylon 612.

[0191] Examples of the polyester resin include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), and derivatives thereof.

[0192] It should be noted that most of the biodegradable resins described below also belong to polyester resins.

[0193] Polyvinylidene chloride resin (PVDC) is a synthetic resin obtained by polymerizing vinylidene groups containing chlorine, and may be a copolymer with vinyl chloride, acrylonitrile, or the like.

[0194] Examples of biodegradable resins include polylactic acid (PLA), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), and 3-hydroxybutyric acid / 3-hydroxyhexanoic acid copolymer (PHBH). Among these, polylactic acid (PLA) and polybutylene succinate (PBS) are preferred, and polybutylene succinate (PBS) is more preferred.

[0195] As the sealant layer, a laminated film in which two or more resins are laminated can be used, and examples thereof include a polyethylene / polypropylene laminated film, a polyamide resin / polyvinylidene chloride resin laminated film, and a polyethylene / polyester resin laminated film.

[0196] When the sealant layer and the barrier layer described below are bonded together with an adhesive, the adhesive used is not particularly limited and may be a solvent-free type, an organic solvent type, an aqueous type, or the like. From the viewpoint of ensuring the shape stability of the paper substrate, it is preferred to use an organic solvent type adhesive or a solvent-free type adhesive.

[0197] As the main component constituting the adhesive, there are exemplified (meth)acrylate copolymers, α-olefin copolymers, ethylene-vinyl acetate copolymers, polyvinyl alcohol, polyurethane, styrene-butadiene copolymers, polyvinyl chloride, epoxy resins, melamine resins, silicone resins, natural rubber, casein, starch, etc. Among these, (meth)acrylate copolymers, ethylene-vinyl acetate copolymers, and polyurethanes are preferred, and polyurethanes are more preferred, from the viewpoint of easy availability and good adhesion.

[0198] As the adhesive, a commercially available adhesive can be used appropriately, and examples thereof include a combination of NIPPOLLAN ID-816 (manufactured by Tosoh Corporation) and HARDENER 300 (manufactured by Tosoh Corporation), and a combination of DICDRY LX-500 (manufactured by DIC Corporation) and DICDRY KW-75 (manufactured by DIC Corporation).

[0199] It should be noted that after applying an adhesive on the sealing layer and the barrier layer, the sealing layer and the barrier layer can be laminated with the paper substrate. After applying an adhesive on the paper substrate, the paper substrate, the sealing layer and the barrier layer can be laminated. In addition, after applying an adhesive on both the sealing layer, the barrier layer and the paper substrate, the two can be laminated. There is no particular limitation. From the viewpoint of shape stability, it is preferred to laminate the paper substrate after applying an adhesive on the sealing layer and the barrier layer.

[0200] The method for applying the adhesive may be appropriately selected from conventionally known methods without particular limitation, and examples thereof include a roll coater, a die coater, a gravure coater, and a spray coater.

[0201] The amount of adhesive applied is not particularly limited, but the amount applied after drying (coating amount) is preferably 1 g / m 2 from the viewpoint of improving the adhesion between the sealing layer, the barrier layer and the paper substrate layer. 2 More preferably 2g / m 2 More preferably 3g / m 2 More than, and preferably 40g / m 2 Below, more preferably 20g / m 2 Below, more preferably 10g / m 2 the following.

[0202] When the sealing layer is formed by the coating liquid, there is no particular limitation on the resin for the sealing layer as long as it has heat sealability, but it is more preferably one or more selected from styrene-butadiene copolymers; olefin / unsaturated carboxylic acid copolymers such as ethylene-acrylic acid copolymers and ethylene-methacrylic acid copolymers; biodegradable resins; polyolefin resins such as polyethylene and polypropylene; and acrylic resins such as methyl acrylate copolymers, methyl methacrylate copolymers, styrene-acrylic acid copolymers, and styrene-methacrylic acid copolymers.

[0203] Among these, at least one selected from styrene-acrylic acid copolymers and olefin / unsaturated carboxylic acid copolymers is more preferred. In the present specification, the acrylic resin does not include olefin / unsaturated carboxylic acid copolymers.

[0204] The olefin / unsaturated carboxylic acid copolymer may be a salt in which a part or all of the carboxyl groups derived from the unsaturated carboxylic acid monomer are neutralized with an alkali metal hydroxide, ammonia, an alkylamine, an alkanolamine, or the like.

[0205] Examples of the olefin monomer of the olefin / unsaturated carboxylic acid copolymer include ethylene, propylene, butadiene, etc. These monomers may be singly or in combination of two or more. Among these, ethylene is preferred.

[0206] As unsaturated carboxylic acid monomers of olefin-unsaturated carboxylic acid copolymers, unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, cinnamic acid, itaconic acid, fumaric acid, maleic acid, butenetricarboxylic acid, etc. can be cited; unsaturated polycarboxylic acid alkyl esters having at least one carboxyl group such as monoethyl itaconate, monobutyl fumarate, monobutyl maleate, etc.; unsaturated sulfonic acid monomers or salts thereof such as acrylamide propanesulfonic acid, sodium salt of sulfoethyl acrylic acid, sodium salt of sulfopropyl methacrylate, etc. can be used alone or in combination of two or more. Among these, unsaturated carboxylic acids are preferred, acrylic acid and methacrylic acid are more preferred, and acrylic acid is particularly preferred.

[0207] Therefore, as the olefin / unsaturated carboxylic acid-based copolymer, at least one of an ethylene-acrylic acid copolymer and an ethylene-methacrylic acid copolymer is preferred.

[0208] The ethylene / unsaturated carboxylic acid copolymer is preferably obtained by emulsion polymerization of ethylene and the unsaturated carboxylic acid monomer. As the ethylene-unsaturated carboxylic acid copolymer, ethylene-acrylic acid copolymer and ethylene-methacrylic acid copolymer are preferred. As long as the effect of the present invention is not impaired, the copolymer may be copolymerized with a monomer formed by other compounds copolymerizable with ethylene and the unsaturated carboxylic acid monomer.

[0209] Specific examples of ethylene / unsaturated carboxylic acid copolymers include ZAIKTHENE (registered trademark) A, ZAIKTHENE (registered trademark) AC (all manufactured by Sumitomo Seika Chemicals, Ltd.), CHEMIPEARL S series (manufactured by Mitsui Chemicals, Inc.), MFHS1279, MP498345N, MP4983R, MP4990R (all manufactured by Michelman Corporation), and the like.

[0210] As the biodegradable resin, preferably one or more selected from polylactic acid (PLA), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polybutylene adipate terephthalate (PBAT) and poly 3-hydroxybutyric acid-3-hydroxyhexanoate (PHBH), more preferably one or more selected from polylactic acid and polybutylene succinate, particularly preferably polylactic acid. The packaging material using a paper substrate has the advantage of reduced environmental load compared to the packaging material formed by a resin film, but by using a biodegradable resin as the sealing layer in the present embodiment, the environmental load can be further reduced.

[0211] The polylactic acid may be a commercially available product or a synthetic product. Examples of the commercially available products include Landy PL-1000 and Landy PL-3000 (aqueous dispersion of polylactic acid, manufactured by MIYOSHIIOIL & FAT CO., LTD.).

[0212] When the sealant layer is provided by coating, the sealant layer coating liquid may contain a lubricant, a pigment, a defoamer, a viscosity modifier, a surfactant, a leveling agent, a colorant, etc. in addition to the sealant layer resin (water-suspended polymer).

[0213] Since these other components tend to deteriorate heat sealability, the total content of the other components is preferably 30% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less in the solid content of the sealant layer.

[0214] From the viewpoint of obtaining high heat-seal peel strength, the content of the sealant layer resin in the solid content of the sealant layer coating liquid is preferably 50 mass % or more, more preferably 60 mass % or more, and even more preferably 70 mass % or more.

[0215] The apparatus used for coating the coating liquid for the sealing layer is not particularly limited, and can be appropriately selected from commonly used coating apparatuses and used. For example, various known coating apparatuses such as an air knife coater, a blade coater, a gravure coater, a rod blade coater, a roll coater, a reverse roll coater, a Meyer rod coater, a curtain coater, a slot die coater, a champlex coater, a metering blade type size press coater, a short dwell coater, a spray coater, a gate roll coater, and a lip coater can be cited.

[0216] The drying conditions of the sealant layer are not particularly limited, but the drying temperature is preferably 50 to 120° C., and the drying time is preferably 5 to 120 seconds.

[0217] The drying equipment for drying the applied sealant layer is not particularly limited, and a known equipment can be used. Examples of the drying equipment include a hot air dryer, an infrared dryer, an explosion-proof dryer, and a hot plate.

[0218] The amount of the sealant layer applied is preferably 1 g / m from the viewpoint of heat seal peel strength. 2 More preferably 2g / m 2 More than, and preferably 30g / m 2 Below, more preferably 20g / m 2 In addition, when the printing paper has two or more sealing layers, it is preferable that the total amount of application is within the above range.

[0219] <Barrier layer>

[0220] The printing paper of this embodiment may further have a barrier layer, and may have the barrier layer on the surface of the paper substrate provided with the printing layer, or may have the barrier layer on the opposite surface. When the barrier layer is provided on the surface of the paper substrate provided with the printing layer, it is preferred that the barrier layer is provided between the paper substrate and the printing layer. In addition, the barrier layer may be provided on the surface opposite to the paper substrate, and when the printing paper has a sealing layer, it is preferred that the barrier layer is provided between the paper substrate and the sealing layer.

[0221] The barrier layer is a layer having the function of mainly preventing the transmission of oxygen. The barrier layer can be formed by coating a coating liquid containing a polymer selected from the group consisting of a water-suspended polymer and a water-soluble polymer, can be formed by laminating a resin having barrier properties by melt extrusion, an adhesive, etc., can form a vapor-deposited layer selected from the group consisting of a metal vapor-deposited layer and an inorganic vapor-deposited layer, and can be formed by laminating a resin film having a vapor-deposited layer selected from the group consisting of a metal vapor-deposited layer and an inorganic vapor-deposited layer.

[0222] (Water-suspended polymer)

[0223] In the present embodiment, the water-suspendable polymer used in the barrier layer refers to a polymer having a solubility of 10 g / L or less in water at 25° C. In the present embodiment, the water-suspendable polymer is preferably derived from a polymer (particles) dispersed in an emulsion.

[0224] There are no particular limitations on the water-suspended polymers and water-soluble resins used in the barrier layer, and examples thereof include polyurethane resins, vinylidene chloride resins, olefin resins, polyester resins, nylon resins, epoxy resins, melamine resins, polyvinyl alcohol resins, acrylonitrile resins, polycarboxylic acid resins, silicone resins, and the like. One type of water-suspended polymer can be used alone, or two or more types can be used in combination. Among them, the water-suspended polymer is preferably at least one selected from the group consisting of polyurethane resins and vinylidene chloride resins. By using these resins to form a barrier layer, excellent gas barrier properties (oxygen barrier properties) can be exerted.

[0225] The polyurethane resin can be manufactured by a known manufacturing method. For example, the polyurethane resin can be obtained by the reaction of a polyisocyanate compound (e.g., a diisocyanate compound) and a polyhydroxy acid (e.g., a dihydroxy acid). In addition, for example, in addition to the above-mentioned polyisocyanate compound and polyhydroxy acid, it can also be obtained by the reaction with a polyol compound (e.g., polyester polyol, polyether polyol) and / or a chain extender.

[0226] The polyurethane resin preferably contains at least one selected from the group consisting of structural units derived from meta-xylene diisocyanate and structural units derived from hydrogenated meta-xylene diisocyanate. Such a polyurethane resin exhibits high cohesion due to the stacking effect of hydrogen bonds and xylylene groups, so the barrier layer becomes easy to exert excellent gas barrier properties. The structural unit derived from meta-xylene diisocyanate refers to a monomer unit in the polyurethane resin in which meta-xylene diisocyanate has reacted. The same is true for structural units derived from hydrogenated meta-xylene diisocyanate and structural units derived from polyisocyanates. A monomer unit refers to a form in which a monomer substance in a polymer has reacted.

[0227] In the polyurethane resin, the total mol% of the structural units derived from meta-xylene diisocyanate and the structural units derived from hydrogenated meta-xylene diisocyanate is preferably 50 mol% or more, more preferably 60 mol% or more, relative to the total amount of the structural units derived from polyisocyanate in the polyurethane resin. The upper limit is not particularly limited, but is preferably 95 mol% or less, more preferably 90 mol% or less. The mol% of the structural units can be obtained by 1 The precipitate can be identified by a known analytical method such as H-NMR.

[0228] The polyurethane resin may have a hydroxyl group, and its hydroxyl value is preferably 50 mgKOH / g or more, more preferably 100 mgKOH / g or more, and further preferably 150 mgKOH / g or more. It should be noted that the upper limit of the hydroxyl value is not particularly limited, and is preferably 1000 mgKOH / g or less, more preferably 800 mgKOH / g or less, and further preferably 600 mgKOH / g or less. If the hydroxyl value of the polyurethane resin is within the above range, the barrier layer becomes easy to exert oxygen barrier properties. In addition, by making the hydroxyl value of the polyurethane resin within the above range, the thermal fusion property of the barrier layer can be improved, and as a result, the heat sealability of the printing paper can also be improved.

[0229] The hydroxyl value was measured in accordance with JIS K0070-1992. When 1 g of a sample was acetylated, the number of mg of potassium hydroxide required to neutralize acetic acid bonded to the hydroxyl group was measured.

[0230] The oxygen permeability of the polyurethane resin at 23°C and relative humidity of 50% when converted to a sheet with a thickness of 25 μm is preferably 100.0 mL / (m 2 ·day·atm) or less, more preferably 50.0mL / (m 2 ·day·atm) or less, more preferably 25.0mL / (m 2 ·day·atm) or less, more preferably 10.0mL / (m 2 ·day·atm) or less, particularly preferably 3.0mL / (m 2 ·day·atm) or less. It should be noted that the oxygen permeability at 23°C and relative humidity of 50% when converted to a sheet with a thickness of 25 μm can be 0 mL / (m 2 ·day·atm).

[0231] It should be noted that the oxygen permeability when converted to a sheet with a thickness of 25 μm means the oxygen permeability measured using a sheet with a thickness of 25 μm formed using the target polyurethane resin. In this specification, the oxygen permeability of the above sheet is measured using an oxygen permeability measuring device (MOCON Co., Ltd., OX-TRAN2 / 22) at 23°C and a relative humidity of 50%.

[0232] The glass transition temperature of the polyurethane resin is preferably 150° C. or lower, more preferably 140° C. or lower, and particularly preferably 135° C. or lower. The glass transition temperature of the polyurethane resin is measured in accordance with JIS K7122:2012.

[0233] As the polyurethane resin, a synthetic product can be used. As the synthetic product, for example, the polyurethane resin described in International Publication No. 2015 / 016069 can be cited. In addition, as the polyurethane resin, a commercial product can be used, for example, "TAKELAC W series (trade name)", "TAKELAC WPB series (trade name)", "TAKELAC WS series (trade name)" manufactured by Mitsui Chemicals, Inc. can be cited, and specifically, TAKELAC WPB-341 is exemplified. As other commercial products, "HPU W-003" (hydroxyl value 235 mgKOH / g) manufactured by Dainichi Seika Industries, Ltd. can be cited.

[0234] Vinylidene chloride resin can be produced by a known production method. For example, vinylidene chloride resin can be obtained by a homopolymer of vinylidene chloride (polyvinylidene chloride, PVDC), a copolymer of vinylidene chloride and a monomer copolymerizable with vinylidene chloride, etc. Monomers copolymerizable with vinylidene chloride are not particularly limited, and examples thereof include vinyl chloride, (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, and butyl (meth)acrylate, acrylonitrile, isobutylene, vinyl acetate, etc.

[0235] As the vinylidene chloride-based resin, commercially available products may be used, and examples thereof include "Saran latex L549B" manufactured by Asahi Kasei Corporation and Diofan B204 manufactured by Solvay.

[0236] The weight average molecular weight of the water-suspendable polymer is preferably 1000 to 20,000,000, and more preferably 5000 to 5,000,000. The weight average molecular weight is a polystyrene-equivalent value measured by gel permeation chromatography.

[0237] The average particle size of the water-suspendable polymer in the emulsion is preferably 0.001 μm or more and 100 μm or less, and more preferably 0.01 μm or more and 10 μm or less. The average particle size can be measured by a dynamic light scattering method.

[0238] (Water-soluble polymer)

[0239] A water-soluble polymer is a resin that is soluble in water. A water-soluble resin is a polymer whose polymer skeleton has a solubility of more than 10 g / L in water at 25°C.

[0240] Examples of the polymer forming the skeleton of the water-soluble polymer include polyvinyl alcohol, modified polyvinyl alcohol, starch and its derivatives, cellulose derivatives, polyvinyl pyrrolidone, polyacrylic acid and its salts, casein, polyethyleneimine, etc. Among these, from the viewpoint of improving the gas barrier properties, the water-soluble polymer is preferably one or more selected from the group consisting of polyvinyl alcohol and modified polyvinyl alcohol, and more preferably modified polyvinyl alcohol.

[0241] As modified polyvinyl alcohol, ethylene-modified polyvinyl alcohol, carboxyl-modified polyvinyl alcohol, silicon-modified polyvinyl alcohol, acetoacetyl-modified polyvinyl alcohol, diacetone-modified polyvinyl alcohol, etc. can be mentioned. Among these, the modified polyvinyl alcohol is preferably selected from one or more of the group consisting of ethylene-modified polyvinyl alcohol, carboxyl-modified polyvinyl alcohol, silicon-modified polyvinyl alcohol and acetoacetyl-modified polyvinyl alcohol, more preferably selected from one or more of the group consisting of ethylene-modified polyvinyl alcohol and carboxyl-modified polyvinyl alcohol, and further preferably ethylene-modified polyvinyl alcohol.

[0242] Polyvinyl alcohol and modified polyvinyl alcohol include completely saponified and partially saponified types, and preferably completely saponified types. Completely saponified means that the degree of saponification exceeds 96%. The degree of saponification is a value measured according to the method of JIS K 6726:1994.

[0243] As the water-soluble polymer, a commercially available item can be used. For example, as a modified polyvinyl alcohol, "Exceval (trade name)" manufactured by Kuraray Co., Ltd., etc. can be mentioned.

[0244] The content of the water-suspendable polymer and the water-soluble polymer in the barrier layer is preferably 10% by mass or more, more preferably 30% by mass or more, further preferably 50% by mass or more, and even more preferably 60% by mass or more, based on the solid content of the barrier layer, from the viewpoint of improving the barrier properties, and the upper limit is 100% by mass.

[0245] It should be noted that the barrier layer may be formed by coating a barrier layer coating liquid on a paper substrate, or by laminating a resin film pre-coated with the barrier layer coating liquid. In addition, the resin film may be a sealant layer.

[0246] When the barrier layer is formed by coating, it is preferred that the barrier layer further contains a layered inorganic compound in addition to at least one selected from the above-mentioned water-suspended polymer and water-soluble polymer. That is, the barrier layer preferably contains a water-suspended polymer and a layered inorganic compound, or contains a water-soluble polymer and a layered inorganic compound. By containing a layered inorganic compound in the barrier layer, the barrier property can be further improved (the oxygen permeability can be further reduced).

[0247] The average length of the layered inorganic compound is preferably 1 μm or more and 100 μm or less, more preferably 2 μm or more and 50 μm or less, and further preferably 3 μm or more and 20 μm or less. Here, the average length of the layered inorganic compound refers to the average length of the major axis in the plane direction of the layered inorganic compound. If the average length is 1 μm or more, the layered inorganic compound in the barrier layer becomes easy to be arranged parallel to the paper substrate. In addition, if the average length is 100 μm or less, there is less concern that a portion of the layered inorganic compound protrudes from the barrier layer.

[0248] The aspect ratio of the layered inorganic compound is preferably 200 or more, more preferably 300 or more, further preferably 500 or more, and further preferably 800 or more. The upper limit of the aspect ratio of the layered inorganic compound is not particularly limited, but is preferably 10,000 or less, more preferably 5,000 or less, and further preferably 2,000 or less.

[0249] When the aspect ratio of the layered inorganic compound is within the above range, the barrier properties are improved, and the coating amount of the barrier layer is reduced, so that the recyclability and lightness of the printing paper can be improved.

[0250] Here, the aspect ratio is a value calculated from a magnified microscope photograph of a cross section of the barrier layer and is an average value (arithmetic mean value of 20 to 30 samples) of values ​​obtained by dividing the length of the layered inorganic compound by its thickness.

[0251] The thickness of the layered inorganic compound is preferably 100 nm or less, more preferably 50 nm or less, and further preferably 30 nm or less. It should be noted that the lower limit of the thickness of the layered inorganic compound is not particularly limited, and is preferably 2 nm or more. Here, the thickness of the layered inorganic compound refers to the average thickness of the layered inorganic compound measured from a microscope magnified photograph of the cross section of the barrier layer (arithmetic mean of 20 to 30 samples). It should be noted that the direction perpendicular to the long axis of the layered inorganic compound is taken as the thickness.

[0252] By making the average thickness of the layered inorganic compound within the above range, the number of layers of the layered inorganic compound in the barrier layer increases, so the barrier layer can exert a higher oxygen barrier property. In particular, if a layered inorganic compound with a large aspect ratio and a small thickness is used, the barrier layer forms a dense film without pores. This phenomenon can also be observed in a microscope magnified photograph of a cross section of the barrier layer.

[0253] As specific examples of layered inorganic compounds, mica, bentonite, kaolinite (kaolin mineral, hereinafter also referred to as "kaolin"), pyrophyllite, talc, montmorillonite, vermiculite, chlorite, seven-angstrom chlorite, serpentine, black hard chlorite, montmorillonite, etc. can be cited. Among these, from the viewpoint of improving water vapor barrier properties, the layered inorganic compound is particularly preferably at least one selected from the group consisting of mica, bentonite and kaolin, and more preferably at least one selected from mica and kaolin. As mica, synthetic mica, muscovite, sericite, phlogopite, biotite, fluorphlogopite (artificial mica), red mica, sodium mica, vanadium mica, illite, titanium mica, sodium mica, brittle mica, etc. can be cited. Among them, as mica, swelling mica is preferred in terms of having a high aspect ratio. In addition, kaolin may be a natural product or a synthetic product (designed kaolin).

[0254] Among these, at least one selected from the group consisting of mica, bentonite and kaolin is preferred, and at least one selected from mica and kaolin is more preferred. The barrier layer contains the above-mentioned layered inorganic compound, thereby more effectively improving the barrier properties of printing paper under high humidity conditions.

[0255] When the barrier layer contains a layered inorganic compound, the content of the layered inorganic compound is not particularly limited, but is preferably 0.5 parts by mass or more and 500 parts by mass or less, more preferably 1 part by mass or more and 300 parts by mass or less, further preferably 2 parts by mass or more and 200 parts by mass or less, further preferably 5 parts by mass or more and 150 parts by mass or less, and particularly preferably 10 parts by mass or more and 70 parts by mass or less, relative to 100 parts by mass of the water-suspended polymer or water-soluble polymer in the barrier layer. By making the content of the layered inorganic compound within the above range, the barrier properties of the printing paper under high humidity conditions can be more effectively improved.

[0256] The barrier layer may contain, in addition to at least one selected from water-suspendable polymers and water-soluble polymers and a layered inorganic compound, a pigment, a dispersant, a surfactant, a defoamer, a wetting agent, a dye, a color adjuster, a thickener, and the like.

[0257] When the barrier layer is provided by coating, the coating amount of the barrier layer coating liquid is preferably 0.1 g / m 2 Above and 10g / m 2 Below, more preferably 0.5g / m 2 Above and 5g / m 2 the following.

[0258] (resin with barrier properties)

[0259] When the barrier layer is formed by laminating a resin having barrier properties by melt extrusion, an adhesive or the like, examples of the resin having barrier properties include ethylene-vinyl alcohol copolymer (EVOH) and MX nylon.

[0260] As EVOH, a commercially available product can be used, and for example, the Eval series manufactured by Kuraray Corporation is exemplified.

[0261] In addition, as MX nylon, MXD6 manufactured by Mitsubishi Gas Chemical Co., Ltd. is exemplified.

[0262] (Evaporated layer)

[0263] As the barrier layer, a vapor-deposited layer may be directly formed on a paper substrate, or a resin film on which a vapor-deposited layer is formed may be laminated to form the barrier layer.

[0264] It should be noted that the vapor-deposited layer is selected from the group consisting of metal vapor-deposited layers and inorganic vapor-deposited layers.

[0265] As the deposited metal of the metal deposited layer, aluminum (Al) is exemplified. Also, as the inorganic compound deposited by the inorganic deposited layer, silicon dioxide (SiOx) and aluminum oxide (AlOx) are exemplified.

[0266] The thickness of the metal vapor-deposited layer is not particularly limited as long as desired barrier properties are obtained.

[0267] As the barrier layer, an adhesive may be applied to a resin film having a vapor-deposited layer and then laminated on a paper substrate.

[0268] Examples of the resin film include polyester resin films such as polyethylene terephthalate (PET), polyamide resin films such as various nylons, polyethylene resins, polypropylene resins, cyclic polyolefin resins, polystyrene resins, acrylonitrile-styrene copolymers (AS resins), acrylonitrile-butadiene-styrene copolymers (ABS resins), polyolefin films such as polybutylene resin films, polyvinyl chloride resins, polycarbonate resins, polyimide resins, polyamideimide resins, polyaryl phthalate resins, silicone resins, polysulfone resins, polyphenylene sulfide resins, polyethersulfone resins, polyurethane resins, cellulose resins, poly(meth)acrylic resins, polyvinylidene chloride films, acetal resin films, fluorine resins, and the like. Polypropylene resins, polyester resins, or polyamide resins are particularly preferred.

[0269] [Printed matter and method for producing printed matter]

[0270] The printed matter of this embodiment is a printed matter obtained from the above-mentioned ultraviolet laser printing medium, and has a printed area of ​​titanium oxide that has changed color in at least a portion. Preferably, the ratio of the Raman intensity of titanium oxide originating from the printed area to the Raman intensity of titanium oxide originating from the non-printed area is 0.70 or less. In addition, the printed area having titanium oxide that has changed color is an area containing titanium oxide that has changed color by irradiation with ultraviolet laser, and is an ultraviolet laser irradiation area, that is, a printed area.

[0271] The method for producing a printed matter according to the present embodiment includes the step of irradiating the printing medium with ultraviolet laser light to change the color of the irradiated region, thereby performing printing.

[0272] As the printing medium used in the method for manufacturing printed matter of the present embodiment, the above-mentioned printing medium is exemplified, and the preferred range is also the same. In addition, in the method for manufacturing printed matter of the present embodiment, as long as the printing layer is set at least in the ultraviolet laser irradiation area, the printing layer may not be set in the non-irradiation area.

[0273] The ultraviolet laser irradiation is preferably performed so that the ratio of the Raman intensity derived from titanium oxide in the printed area to the Raman intensity derived from titanium oxide in the non-printed area becomes 0.70 or less.

[0274] It should be noted that in the printed matter, the printing area refers to the area (portion) containing the discolored titanium oxide in the printable area, and the area (portion) printed by the ultraviolet laser. The non-printing area refers to the area (portion) that is not printed in the printable area. In addition, the printable area refers to the entire area containing titanium oxide in the ultraviolet laser printing paper or printed matter, which combines the area that can be printed based on the ultraviolet laser and the area (portion) printed by the ultraviolet laser in the case where there is a situation, and the non-printable area refers to the area other than the printable area in the ultraviolet laser printing paper or printed matter.

[0275] Printing is preferably performed in such a manner that the ratio of the Raman intensity of titanium oxide in the printed area to the Raman intensity of titanium oxide in the non-printed area (Raman intensity in the printed area / Raman intensity in the non-printed area) is 0.70 or less. By making the Raman intensity ratio within the above range, a printed material with excellent visibility is obtained.

[0276] Regarding the above Raman intensity ratio (Raman intensity of the printed area / Raman intensity of the non-printed area), when rutile titanium oxide is used as titanium oxide, the Raman intensity derived from titanium oxide is 447±10 cm -1In addition, when anatase titanium oxide is used as titanium oxide, the Raman intensity derived from titanium oxide is compared with 516±10 cm -1 The maximum Raman intensity in the wavenumber range.

[0277] In addition, when rutile titanium oxide and anatase titanium oxide coexist, the comparison is made based on the Raman intensity derived from rutile titanium oxide.

[0278] The printed matter obtained in the present embodiment preferably has a white non-printing area and a black printing area.

[0279] The non-printed area preferably has a lightness of 10 in the Munsell colorimetric system, that is, white. On the other hand, the printed area preferably has a lightness of 0 to 8 in the Munsell colorimetric system, more preferably 0 to 6, and even more preferably 0 to 4.

[0280] In order to obtain the color in the above-mentioned Munsell colorimetric system, it is preferred to appropriately adjust the titanium oxide content of the printing layer in the printing paper, the crystallite size of titanium oxide, the length-weighted average fiber length of the pulp constituting the paper substrate, other characteristics (type of titanium oxide, diffraction angle, ratio of the number of fine fibers in the pulp constituting the paper substrate, water retention value of the pulp constituting the paper substrate, the blending amount of inorganic pigments, thickness of the printing layer, etc.), and the irradiation conditions of the ultraviolet laser (such as average output, number of repetition frequencies, wavelength, etc.).

[0281] [Ultraviolet laser irradiation conditions]

[0282] From the viewpoint of improving the visibility of the printed area, the wavelength of the ultraviolet laser is preferably 370 nm or less, more preferably 365 nm or less, further preferably 360 nm or less, and is preferably 260 nm or more, more preferably 340 nm or more, further preferably 350 nm or more.

[0283] The average output of the ultraviolet laser is preferably 0.3 W or more, more preferably 0.8 W or more, further preferably 1.2 W or more, and further preferably 1.8 W or more from the viewpoint of improving the visibility of the printed area, and is preferably 30 W or less, more preferably 25 W or less, further preferably 20 W or less, further preferably 15 W or less, further preferably 10 W or less, and further preferably 6 W or less from the viewpoint of economy.

[0284] The repetition rate (frequency) of the ultraviolet laser is preferably above 10 kHz, more preferably above 20 kHz, further preferably above 30 kHz, and is preferably below 100 kHz, more preferably below 80 kHz, further preferably below 60 kHz, from the viewpoint of improving the visibility of the printed area.

[0285] The spot diameter of the ultraviolet laser is preferably 10 μm or more, more preferably 20 μm or more, further preferably 30 μm or more, and is preferably 300 μm or less, more preferably 240 μm or less, further preferably 180 μm or less, further preferably 120 μm or less, from the viewpoint of obtaining a clear image and easiness of printing.

[0286] The scanning speed of the ultraviolet laser is preferably 500 mm / second or more, more preferably 1000 mm / second or more, further preferably 2000 mm / second or more, and preferably 7000 mm / second or less, more preferably 6000 mm / second or less, further preferably 5000 mm / second or less, from the viewpoint of high-speed printing and visibility of the printed area.

[0287] The spacing (line pitch) of the entire surface coating of the ultraviolet laser is preferably greater than 10 μm, more preferably greater than 20 μm, and further preferably greater than 30 μm, and is preferably less than 300 μm, more preferably less than 250 μm, and further preferably less than 200 μm, from the viewpoint of obtaining a clear image and the ease of obtaining the device.

[0288] [Method of manufacturing printed matter]

[0289] The method for producing a printed matter of the present invention can be carried out in various ways.

[0290] Various forms of the method for producing a printed matter to which the present embodiment is applicable are exemplified below, but the method for producing a printed matter in the present embodiment is not limited to the following forms. The information to be printed is not particularly limited, but is preferably variable information.

[0291] The method for producing a printed matter according to the present embodiment is preferably performed in-line.

[0292] (1) Direct printing on packaging

[0293] A first embodiment of the method for producing printed matter of the present embodiment is a method for printing information on a package having the printing paper of the present embodiment, and comprises the following steps: directly printing on a package moving on a packaging production line or during intermittent stop under ultraviolet laser.

[0294] The first printed article is produced by making a package from the ultraviolet laser printing paper of this embodiment and directly printing it under ultraviolet laser. It should be noted that at least the outermost layer of the printed area of ​​the package is made of the aforementioned printing paper.

[0295] In addition, examples of the packaging body include corrugated cardboard, boxes, and the like, and it is preferred that the printing be performed directly on the side surface or the upper surface of the packaging body under ultraviolet laser.

[0296] In addition, the packaging line may also have a coating (applying) mechanism. Examples of the coating mechanism include a contact printer, a letterpress printer, and a spray coater.

[0297] This method includes the following steps: a step of applying a printed layer to a package body by a coating mechanism while the package body is moving on a packaging production line; and a step of directly printing the package body with an ultraviolet laser while the package body is moving on the packaging production line or is stopped intermittently, further downstream.

[0298] (2) Printing of labels

[0299] A second embodiment of the method for producing a printed matter according to the present embodiment is a method for printing information on a label having the printing paper according to the present embodiment. The printing paper constituting the printing surface of the label is the printing paper according to the present embodiment.

[0300] The printed label is preferably affixed to the package body using a label affixing device. Various label affixing devices have been proposed as label affixing devices. It should be noted that, in this case, there is a printed layer on the surface irradiated with ultraviolet rays.

[0301] As the first label sticking device, an adhesive is applied to the label base paper wound into a roll and then affixed to an article. More specifically, the following roll labeling machine can be exemplified, which comprises: a cutting unit that cuts each sheet of the label base paper wound into a roll into a predetermined length; an adhesive conveying unit that receives the label base paper cut by the cutting unit by a label base paper holder coated with an adhesive, and makes the adhesive adhere to the back of the label base paper; and an attaching unit that receives the label base paper (label) to which the adhesive is applied by the adhesive conveying unit and affixes it to an article such as a container, wherein a rotating conveying unit having a label holding surface on the outer surface is provided between the cutting unit and the adhesive conveying unit, and an example of which can be exemplified is Japanese Patent Publication No. 6-64637.

[0302] In addition, there can be exemplified a roller labeling machine having a cutting unit for cutting each label base paper wound into a roll into a predetermined length, a delivery roller for transmitting to a pasting roller, and an adhesive roller for applying glue to the label base paper held by the pasting roller; a method that does not require the aforementioned delivery roller.

[0303] The ultraviolet laser irradiation is preferably performed before the label base paper wound into a roll is cut into a predetermined length, or after being cut and before being transferred to the next roll, etc. According to the roll labeling machine method, the surface or back side of the label base paper wound into a roll becomes the surface or back side when attached to the package body, and therefore, the ultraviolet laser irradiation is performed accordingly.

[0304] The second label pasting device uses an adhesive label roll as the label. In this case, at least on the surface opposite to the surface to which the adhesive is applied, that is, the surface irradiated with the ultraviolet laser, there is a printing layer.

[0305] In the case of using an adhesive label roll with a release paper, for example, the following adhesion device can be exemplified: a release paper separation unit that separates the adhesive label from the release paper; a transfer roller that receives the adhesive label from which the release paper has been separated; and a pasting roller that attracts the adhesive label by the transfer roller and pastes it on an article (package). Based on the irradiation of the ultraviolet laser, it is preferably carried out before separating the release paper, or after separating the release paper and before loading it on the pasting roller.

[0306] In addition, the following device can be exemplified: a device having a mechanism for mounting an adhesive label roll with a release paper and separating the release paper from the adhesive label, a mechanism for pasting the label just after separation, and a device for printing with an ultraviolet laser during the period until the mounted adhesive label roll is separated from the release paper. The above method of pasting the adhesive label is also called unidirectional installation (in Japanese: 流し貼り).

[0307] Furthermore, the following label adhesion device can be exemplified: a device having a mechanism for mounting an adhesive label roll with a release paper and separating the release paper from the adhesive label, a mechanism for pasting the adhesive label on an article (package), and the aforementioned pasting mechanism is a syringe method, an air jet method, or a robotic arm method. Based on the irradiation of the ultraviolet laser, it is preferably carried out during the period until the release paper is separated from the mounted adhesive label roll with a release paper.

[0308] As the label, a label without a liner can also be used. A label without a liner is a label without a release paper, and compared with the case of using an adhesive label roll with a release paper, it has the following characteristics: the number of label sheets per roll is large, there is no release paper, so it is inexpensive. When using a label without a liner, a printing layer is formed on the surface opposite to the surface to which the adhesive is applied, that is, the surface irradiated with the ultraviolet laser.

[0309] As a label adhesion device using a label without a liner, the following device can be exemplified: a device having a mechanism for mounting a label roll without a gasket, a cutting mechanism for cutting each one of the labels without a gasket, and a pasting mechanism for pasting the cut labels without a gasket on an article (package), and the aforementioned pasting mechanism is a barrel method or a robotic arm method. Preferably: printing by ultraviolet laser irradiation is carried out between the mechanism for mounting the label roll without a gasket and the cutting mechanism, or during the period of transporting the cut labels without a gasket to the pasting mechanism.

[0310] For the third label adhesion device, after pasting the printing paper of the present embodiment on an article (package), printing is carried out under ultraviolet laser.

[0311] As a method of attaching the label, refer to the above-mentioned first device and second device.

[0312] (3) Printing on adhesive tape

[0313] The third embodiment of the method for producing a printed article of the present embodiment is a mode in which a printing paper is formed into an adhesive tape. In this case, a printing layer is provided on the surface opposite to the surface to which the adhesive is applied.

[0314] That is, the method for producing printed matter of the third embodiment includes a step of attaching the adhesive tape made of the printing paper to an article (package), and a step of printing with an ultraviolet laser before or after the attaching step.

[0315] Alternatively, a printing device in which an ultraviolet laser printing device is installed in a corrugated cardboard sealing machine may be used. Specifically, the printing device includes a mechanism for installing a tape winding device and a conveyor for conveying corrugated cardboard, a mechanism for folding a baffle plate into the corrugated cardboard, a mechanism for attaching the tape to seal the corrugated cardboard, and a mechanism for printing on the tape under ultraviolet laser during or after attaching the tape.

[0316] The method for producing a printed matter according to the present embodiment is not limited to the above-described method, and can be used for various applications requiring printing.

[0317] In the present embodiment, the printed matter obtained by the above-described method for producing a printed matter is suitable for use in packaging, labels, adhesive tapes, and the like.

[0318] Examples of packaging bodies include outer packaging bags, outer packaging boxes, milk packaging, aseptic paper packaging, paper cups and other liquid containers for beverages (preferably liquid paper containers for beverages), and skin packaging; examples of labels include label base paper, adhesive labels, and adhesive sheets; and examples of adhesive tapes include adhesive tapes and kraft belts.

[0319] [Processed products]

[0320] The ultraviolet laser printing paper and printed matter of this embodiment are used for various processed products. That is, the processed product of this embodiment is made by using the ultraviolet laser printing paper of this embodiment or the printed matter of this embodiment.

[0321] As the processed product of this embodiment, a package, a label, an adhesive tape, etc. are suitable.

[0322] Examples of packaging bodies include inner lining paper of corrugated cardboard (especially the outermost inner lining paper), outer packaging bags, outer packaging boxes, milk packaging, aseptic paper packaging, liquid containers for beverages such as paper cups (preferably liquid paper containers for beverages), food trays, skin packaging, pillow packaging, self-supporting bags, three-way / four-way sealed packaging, etc.; examples of labels include label paper, adhesive labels, and adhesive sheets; and examples of adhesive tapes include adhesive tapes and kraft belts.

[0323] like Figure 1 As shown, a liquid container 10 as an example of a package has, for example, a printed area 20 on its surface. The printed area 20 is irradiated with ultraviolet laser light, and characters such as a date are printed.

[0324] [Ink composition]

[0325] The ink composition of this embodiment is used to form a printed layer that changes color by irradiation with ultraviolet laser, and the printed layer contains titanium oxide with a crystallite size of 30 nm or more. By printing an ultraviolet laser print medium having a printed layer formed by the ink composition of this embodiment by irradiation with ultraviolet laser, an image with excellent print clarity per dot is obtained.

[0326] As examples of the titanium oxide contained in the ink composition and its content, the titanium oxide contained in the printing layer of the above-mentioned ultraviolet laser printing paper and the titanium oxide content in the coating liquid are exemplified, and the preferred ranges are also the same.

[0327] In addition, as other components contained in the ink composition, it may contain various components that the above-mentioned coating liquid optionally contains, such as thermoplastic resins, inorganic pigments, film-forming agents, pigment dispersants, pigment dispersion resins, anti-blocking agents, wetting agents, viscosity regulators, pH regulators, defoaming agents, general surfactants and the like, and the preferred method thereof is the same as the preferred method of the above-mentioned coating liquid.

[0328] Example

[0329] The following examples and comparative examples are listed to further specifically illustrate the features of the present invention. The materials, dosages, ratios, processing contents, processing steps, etc. shown in the following examples can be appropriately changed without departing from the gist of the present invention. Therefore, the scope of the present invention should not be limited to the restrictive interpretation of the specific examples shown below. It should be noted that "parts" and "%" refer to "parts by mass" and "% by mass" unless otherwise specified.

[0330] [Titanium oxide]

[0331] The titanium oxide used in Examples and Comparative Examples is shown in Table 1 below.

[0332] [Table 1]

[0333] Table 1

[0334]

[0335] <Method for synthesizing titanium oxides C, F to H>

[0336] Titanium tetraisopropoxide (TTIP) is hydrolyzed and polycondensed to synthesize titanium oxide (amorphous), which is then calcined to crystallize.

[0337] Specifically, it is synthesized through the following steps (1) to (6).

[0338] (1) The following solutions A to C were prepared using TTIP (manufactured by Tokyo Chemical Industry Co., Ltd., product number: T0133), isopropyl alcohol (manufactured by Tokyo Chemical Industry Co., Ltd., purity 99.5% or more, product number: I0163) and ion-exchanged water.

[0339] Solution A: TTIP 35.6 parts by mass, isopropanol 200 parts by mass

[0340] Solution B: 200 parts by mass of isopropyl alcohol, 6.3 parts by mass of ion exchange water

[0341] Solution C: 200 parts by mass of isopropyl alcohol, 24.4 parts by mass of ion exchange water

[0342] (2) Solution B was slowly added dropwise to Solution A while stirring with a Teflon (registered trademark) stirring blade, and stirring was continued for 10 minutes.

[0343] (3) Solution C was slowly added dropwise to the mixed solution of Solution A and Solution B obtained in (2) above, and the mixture was stirred for 1 minute and then allowed to stand at room temperature for 24 hours.

[0344] (4) The precipitate was separated into solid and liquid using a membrane filter (manufactured by Advantec, material: cellulose acetate).

[0345] (5) After washing with isopropyl alcohol, the mixture was dried at 100° C. for 5 hours to obtain titanium oxide (amorphous).

[0346] (6) Firing is performed in a muffle furnace to crystallize titanium oxide.

[0347] The calcination temperature was set at the temperature in the table, and the calcination was performed at a temperature increase rate of 10° C. / min and over 2 hours after the temperature increase.

[0348] [Example 1-1]

[0349] <Manufacturing of paper substrate>

[0350] A pulp slurry of hardwood bleached kraft pulp (LBKP, α-cellulose: 86%) was beaten with a double disc refiner until the dissociation freeness (CSF: Canadian standard freeness) was 450 mL to obtain a pulp slurry. 0.30 parts (in terms of solid content) of an amphoteric polyacrylamide-based reinforcing agent (DS4430 manufactured by Seiko PMC Co., Ltd.) as an internal reinforcing agent, 0.5 parts (in terms of solid content) of a rosin sizing agent (SIZEPINE N-811 manufactured by Arakawa Chemical Industries, Ltd.) as an internal sizing agent, and 1.0 parts (in terms of solid content) of aluminum sulfate were added to 100 parts of the obtained pulp slurry to prepare a paper stock. The paper stock was adjusted to a basis weight of 40 g / m 2 The paper was made using a long-wire Yankee paper machine. The basis weight of the paper substrate obtained was 40 g / m 2 , thickness 51μm, density 0.78g / cm 3 .

[0351] <Preparation of coating solution>

[0352] As shown in Table 2, 68 parts of titanium oxide A and 32 parts of ion exchange water were mixed to a solid content concentration of 68%. Then, a pigment dispersion was prepared using a Cowles disperser, and 3691.4 parts (1291.9 parts in terms of solid content) of ethylene-acrylic emulsion (CHEMIPEARL S-300 manufactured by Mitsui Chemicals, Inc., solid content concentration 35%) were added as an emulsion to prepare a coating liquid with a solid content concentration of 35.9%. Then, the coating liquid was diluted with ion exchange water to adjust the solid content concentration to 35.0%.

[0353] <Manufacturing of UV laser printing paper>

[0354] The coating liquid prepared as described above was applied to a paper substrate using a Meyer bar so that the coating amount of titanium oxide became the coating amount described in Table 2, and dried at 140° C. for 1 minute to form a printing layer, thereby obtaining ultraviolet laser printing paper.

[0355] It should be noted that the printing layer is applied on the smoother surface of the paper substrate.

[0356] [Examples 1-2 to 1-8, Comparative Examples 1-1, 1-2]

[0357] In the preparation of the coating liquid, except that the titanium oxide used was changed to the titanium oxide described in Table 2, the same procedure as in Example 1-1 was carried out to obtain ultraviolet laser printing paper.

[0358] [Examples 1-9]

[0359] In the preparation of the coating liquid, the addition amount of the ethylene-acrylic acid emulsion was changed to 19234.3 parts (6732.0 parts in terms of solid content), and the coating was performed on the paper substrate in such a manner that the content of titanium oxide in the printed layer became the content (weight per unit area) recorded in Table 2. Otherwise, the same procedure as in Example 1-4 was followed to obtain paper for ultraviolet laser printing.

[0360] [Examples 1-10]

[0361] In the preparation of the coating liquid, the addition amount of the ethylene-acrylic acid emulsion was changed to 582.9 parts (204.0 parts in terms of solid content), and the coating was performed on the paper substrate in such a manner that the content of titanium oxide in the printed layer became the content (weight per unit area) recorded in Table 2. Otherwise, the same procedure as in Example 1-4 was followed to obtain paper for ultraviolet laser printing.

[0362] [Examples 1-11]

[0363] In the preparation of the coating liquid, the addition amount of the ethylene-acrylic acid emulsion was changed to 237.5 parts (83.1 parts in terms of solid content), and the coating was performed on the paper substrate in such a manner that the content of titanium oxide in the printed layer became the content (weight per unit area) recorded in Table 2. Otherwise, the same procedure as in Example 1-4 was followed to obtain paper for ultraviolet laser printing.

[0364] [Examples 1-12]

[0365] In the preparation of the coating liquid, the addition amount of the ethylene-acrylic acid emulsion was changed to 1748.6 parts (612.0 parts in terms of solid content), and the coating was performed on the paper substrate in such a manner that the content of titanium oxide in the printed layer became the content (weight per unit area) recorded in Table 2. Otherwise, the same procedure as in Example 1-4 was followed to obtain paper for ultraviolet laser printing.

[0366] [Examples 1-13]

[0367] In the preparation of the coating liquid, the addition amount of the ethylene-acrylic acid emulsion was changed to 1020.0 parts (357.0 parts in terms of solid content), and the coating was performed on the paper substrate in such a manner that the content of titanium oxide in the printed layer became the content (weight per unit area) recorded in Table 2. Otherwise, the same procedure as in Example 1-4 was followed to obtain paper for ultraviolet laser printing.

[0368] [Examples 1-14]

[0369] In the preparation of the coating liquid, the addition amount of the ethylene-acrylic acid emulsion was changed to 9520.0 parts (3332.0 parts in terms of solid content), and the coating was performed on the paper substrate in such a manner that the content of titanium oxide in the printed layer became the content (weight per unit area) recorded in Table 2. Otherwise, the same procedure as in Example 1-4 was followed to obtain paper for ultraviolet laser printing.

[0370] [Examples 1-15]

[0371] In the manufacture of the paper substrate, 30 parts of hardwood bleached kraft pulp (LBKP, α-cellulose: 86%) and 70 parts of softwood bleached kraft pulp (NBKP, α-cellulose: 85%) were mixed and beaten in a manner such that the dissociation freeness became 550 mL and used. Except for this, the ultraviolet laser printing paper was obtained in the same manner as in Example 1-4.

[0372] [Examples 1-16]

[0373] In the production of the paper substrate, an ultraviolet laser printing paper was obtained in the same manner as in Example 1-4 except that 100 parts of softwood bleached kraft pulp (NBKP, α-cellulose: 86%) was beaten to a dissociation freeness of 580 mL.

[0374] [Example 1-17]

[0375] In the manufacture of the paper substrate, 70 parts of the same hardwood bleached kraft pulp (LBKP) as in Example 1-4 and 30 parts of powder pulp made from the LBKP as described below are used, and the mixture is beaten in such a way that the dissociation freeness becomes 400 mL and used. Except for this, the ultraviolet laser printing paper is obtained in the same manner as in Example 1-4.

[0376] <Powder pulp>

[0377] The powder pulp was prepared by mechanically pulverizing dry flakes of hardwood bleached kraft pulp (LBKP) using a chopper (manufactured by Lintec Corporation, HA8 2542 30E, screen size 0.24 mm).

[0378] [Examples 1-18]

[0379] In the production of paper substrate, hardwood dissolving pulp (LBDP, α-cellulose: 94%) was papered in a pulper and dried to form dry pulp. The dry pulp was further dissociated and beaten to a degree of dissociation of 550 mL before use. The same procedure as in Example 1-4 was used to obtain ultraviolet laser printing paper.

[0380] [Example 1-19]

[0381] In the preparation of the coating liquid, 20 parts of titanium oxide D shown in Table 2 in terms of solid content and 70 parts of calcium carbonate (manufactured by FIMATEC LTD., product number: FMT-97W, heavy calcium carbonate, average particle size 0.95 μm (catalog value), amorphous) were mixed, 0.08 parts of sodium polyacrylate as a dispersant was added, and then ion exchange water was added to adjust the solid content concentration to 67.5%. Then, a pigment dispersion was prepared using a Cowles disperser, and 10 parts of styrene-butadiene latex (manufactured by NIPPON A&L LNC., product number: PB5453) in terms of solid content was added to prepare a coating liquid having a solid content concentration of 62.3%. The coating liquid prepared as above was applied to the paper substrate used in Example 4 using an air knife coater so that the content of titanium oxide in the printing layer became the content (weight per unit area) described in Table 2. The same procedure as in Example 1-4 was followed except that ultraviolet laser printing paper was obtained.

[0382] [Examples 1-20]

[0383] Ultraviolet laser printing paper was obtained in the same manner as in Example 1-19 except that kaolin (manufactured by Tiele, KAOFINE90, plate-like particles, average particle size 0.21 μm (catalog value)) was used instead of calcium carbonate.

[0384] [Example 1-21]

[0385] <Masterbatch manufacturing method>

[0386] According to Japanese Patent Application Laid-Open No. 2015-96568, a masterbatch was prepared by the following steps.

[0387] 60 parts of PE resin (polyethylene resin, manufactured by Japan Polyethylene Co., Ltd., LC522) and 40 parts of titanium oxide D were mixed in a tumble mixer (manufactured by EISHIN Co., Ltd., TM-65S) at 45 rpm for 1 hour, and then melt-kneaded in a twin-screw extruder (manufactured by Japan Steel Works, Ltd., TEX30XCT, L / D=42) at a screw speed of 250 rpm and a barrel temperature of 200°C. The mixture was extruded into a strand shape, cooled in a water tank, and pelletized into a columnar shape with an average axial diameter of 2.0 mm and an average axial length of 3.0 mm using a pelletizer to obtain a masterbatch.

[0388] (Provision of lamination layer (film))

[0389] The masterbatch and the PE resin were fed into a single screw extruder (50C150 manufactured by Toyo Seiki Seisaku-sho, Ltd.) so that the content of titanium oxide in the printed layer when a printed layer of 20 μm was formed became the value shown in Table 2, and the laminated layer as the printed layer was melt-laminated on the surface of the paper substrate used in Example 1-1 by extrusion lamination so that the thickness of the laminated layer as the printed layer became 20 μm, and then rapidly cooled while being clamped by a cooling roll whose temperature was adjusted to 20° C., thereby obtaining ultraviolet laser printing paper having a laminated layer as the printed layer. It should be noted that the melting temperature was set to 320° C.

[0390] [Example 1-22]

[0391] <Preparation of coating solution>

[0392] In the preparation of the coating liquid, 16.1 parts of titanium oxide D as shown in Table 2 in terms of solid content are mixed with 100 parts by mass of a medium for gravure ink (Lamy CP medium manufactured by DIC Corporation, resin component: nitrocellulose, solid content concentration: 24.1%), and a Cowles disperser is used to prepare an ink for gravure printing having a titanium oxide concentration of 40% by mass in the solid content.

[0393] <Manufacturing of UV laser printing paper>

[0394] Use gravure printing machine (10-color machine, plate depth: 50μm, drying temperature after printing 80℃, printing speed 80m 2 / min) to obtain the titanium oxide contents in the table, the paper substrate of Example 1-1 was printed. It should be noted that a three-color printing plate was used to obtain the titanium oxide contents in the table.

[0395] [Comparative Examples 1-3]

[0396] <Preparation of coating solution>

[0397] 68 parts of titanium oxide D as shown in Table 2 and 32 parts of ion exchange water were mixed to a solid content concentration of 68%. Then, a pigment dispersion was prepared using a Cowles disperser, and 42980 parts (15043 parts in terms of solid content) of an ethylene-acrylic emulsion (CHEMIPEARL S-300 manufactured by Mitsui Chemicals, Inc., solid content concentration 35%) was added as an emulsion to prepare a coating liquid with a solid content concentration of 35.9%. Then, the coating liquid was diluted with ion exchange water to adjust the solid content concentration to 35.1%.

[0398] Ultraviolet laser printing paper was obtained in the same manner as in Example 1-4 except that the printing layer was coated on a paper substrate so that the content of titanium oxide in the printing layer became the content (weight per unit area) described in Table 2.

[0399] [Example 2-1]

[0400] A paper base was produced in the same manner as in Example 1-1, and a printed layer was formed in the same manner as in Example 1-1.

[0401] <Formation of sealing layer>

[0402] PE (low-density polyethylene, manufactured by Japan Polyethylene Co., Ltd., NOVATEC (registered trademark) LD LC522) was put into a single screw extruder (manufactured by Toyo Seiki Seisaku-sho Co., Ltd., D2025), extrusion laminated (melt laminated) on the opposite side of the paper substrate to the side provided with the printing layer in such a manner that the thickness of the resin became 15 μm, and then rapidly cooled while being clamped by a cooling roll adjusted to a temperature of 20° C., and a sealing layer was provided to obtain ultraviolet laser printing paper. It should be noted that the melting temperature of the resin in the extrusion lamination was set to 320° C.

[0403] [Examples 2-2 to 2-8, Comparative Examples 2-1, 2-2]

[0404] In the preparation of the coating liquid, except that the titanium oxide used was changed to the titanium oxide described in Table 3, the same procedure as in Example 2-1 was carried out to obtain ultraviolet laser printing paper.

[0405] [Example 2-9 to Example 2-22]

[0406] Ultraviolet laser printing papers were obtained in the same manner as in Examples 1-9 to 1-22 except that a seal layer was provided in the same manner as in Example 2-1.

[0407] [Example 2-23]

[0408] <Manufacturing of paper substrate, preparation of coating liquid and formation of printed layer>

[0409] A printed layer was formed on the paper base layer in the same manner as in Example 2-4.

[0410] <Formation of sealing layer>

[0411] On the surface of PE film (linear low-density polyethylene film (LLDPE), manufactured by FUTAMURA CHEMICAL CO., LTD., LL-XLTN, thickness 25 μm) 2 After applying an isocyanate adhesive (10 parts of DICDRYLX-500 manufactured by DIC Corporation, mixed with 1 part of DICDRY KW-75 manufactured by DIC Corporation), the paper substrate side of the paper substrate having the printed layer formed thereon was laminated to obtain ultraviolet laser printing paper.

[0412] [Example 2-24]

[0413] <Manufacturing of paper substrate, preparation of coating liquid and formation of printed layer>

[0414] A printed layer was formed on the paper base layer in the same manner as in Example 2-4.

[0415] <Formation of sealing layer>

[0416] A sealant layer was formed in the same manner as in Example 2-4, to obtain ultraviolet laser printing paper, except that PE was changed to PP (polypropylene, manufactured by Mitsubishi Chemical Corporation, NOVATEC PP MA-3) and the melting temperature was changed to 330°C.

[0417] [Example 2-25]

[0418] <Manufacturing of paper substrate, preparation of coating liquid and formation of printed layer>

[0419] A printed layer was formed on the paper base layer in the same manner as in Example 2-4.

[0420] <Formation of sealing layer>

[0421] A UV laser printing paper was obtained by forming a seal layer in the same manner as in Example 2-23 except that the PE film was changed to a CPP film (unstretched polypropylene film, manufactured by FUTAMURA CHEMICAL CO., LTD., FHK2-L, thickness 25 μm). The film was a laminated film of CoPP (co-polypropylene) / CoPP (co-polypropylene) / special PP, and the CoPP surface, which was a corona-treated surface, was on the paper substrate side.

[0422] [Example 2-26]

[0423] <Manufacturing of paper substrate, preparation of coating liquid and formation of printed layer>

[0424] A printed layer was formed on the paper base layer in the same manner as in Example 2-4.

[0425] <Formation of sealing layer>

[0426] Water was added to a water-based heat sealant (ethylene-acrylic acid copolymer (Et-AA in the table), MFHS1279 manufactured by Michelman, Inc., solid content concentration 42%) to dilute the solid content concentration to 20%, and a Meyer rod was used to coat the mixture in an amount (solid content) of 5 g / m 2 The method was to apply the coating on the surface of the paper substrate opposite to the surface provided with the printing layer, and dry it at 120° C. for 60 seconds to form a sealing layer to obtain ultraviolet laser printing paper.

[0427] [Example 2-27]

[0428] <Manufacturing of paper substrate, preparation of coating liquid and formation of printed layer>

[0429] A printed layer was formed on the paper base layer in the same manner as in Example 2-4.

[0430] <Formation of sealing layer>

[0431] A sealing layer was formed in the same manner as in Example 2-26, to obtain ultraviolet laser printing paper, except that a water-based heat sealant (ethylene-methacrylic acid copolymer (Et-MAA in the table), manufactured by Mitsui Chemicals, Inc., CHEMIPEARL S-300, solid content concentration 35%) was adjusted to a solid content concentration of 20% and used.

[0432] [Example 2-28]

[0433] <Manufacturing of paper substrate, preparation of coating liquid and formation of printed layer>

[0434] A printed layer was formed on the paper base layer in the same manner as in Example 2-4.

[0435] <Formation of sealing layer>

[0436] A sealing layer was formed in the same manner as in Example 2-26, to obtain ultraviolet laser printing paper, except that a water-based heat sealant (styrene-acrylic acid copolymer (St-AA in the table), manufactured by Seiko PMC Co., Ltd., SEIKOAT RE-2016, solid content concentration 35%) was adjusted to a solid content concentration of 20%.

[0437] [Example 2-29]

[0438] <Manufacturing of paper substrate, preparation of coating liquid and formation of printed layer>

[0439] A printed layer was formed on the paper base layer in the same manner as in Example 2-4.

[0440] <Formation of barrier layer>

[0441] EVOH (ethylene-vinyl alcohol copolymer, manufactured by Kuraray Co., Ltd., Eval E105B) was introduced into a single screw extruder (manufactured by Toyo Seiki Seisaku-sho, Ltd., D2025), extrusion laminated (melt laminated) on the opposite side of the paper substrate to the surface provided with the printed layer so that the thickness of the resin was 15 μm, and then rapidly cooled while being sandwiched with a cooling roll adjusted to a temperature of 20° C. to form a barrier layer. It should be noted that the melt temperature of the resin in the extrusion lamination was set to 215° C.

[0442] <Formation of sealing layer>

[0443] A sealing layer was provided in the same manner as in Example 2-4 to obtain ultraviolet laser printing paper.

[0444] [Example 2-30]

[0445] <Manufacturing of paper substrate, preparation of coating liquid and formation of printed layer>

[0446] A printed layer was formed on the paper base layer in the same manner as in Example 2-4.

[0447] <Formation of barrier layer>

[0448] 50 parts of an aqueous dispersion of a layered inorganic compound (layered inorganic compound = synthetic mica (swelling mica, average length: 6.3 μm, aspect ratio: about 1000, thickness: about 5 nm), solid content concentration 6%, NTO-05 manufactured by TOPY INDUSTRIES LIMITED.) were added to 100 parts of an aqueous solution of ethylene-modified polyvinyl alcohol (completely saponified type, manufactured by Kuraray Co., Ltd.) having a solid content concentration of 15% by mass, and further dilution water was added thereto to adjust the solid content concentration to 10% by mass to form a coating solution for a barrier layer. A Meyer bar was used to coat the mixture in an amount of 2.0 g / m 2 The barrier layer coating liquid is applied in a manner, and then dried in a hot air dryer at 120° C. for 1 minute to form a barrier layer.

[0449] <Formation of sealing layer>

[0450] A sealing layer was provided in the same manner as in Example 2-4 to obtain ultraviolet laser printing paper.

[0451] [Example 2-31]

[0452] <Manufacturing of paper substrate, preparation of coating liquid and formation of printed layer>

[0453] A printed layer was formed on the paper base layer in the same manner as in Example 2-4.

[0454] <Formation of barrier layer>

[0455] To an aqueous dispersion of a layered inorganic compound (layered inorganic compound = synthetic mica (swelling mica, average length: 6.3 μm, aspect ratio: about 1000, thickness: about 5 nm), solid content concentration 6 mass%, manufactured by TOPY INDUSTRIES LIMITED., NTO-05), a urethane emulsion (solid content concentration 30 mass%, glass transition temperature 130°C, oxygen permeability when forming a sheet with a thickness of 25 μm of 2.0 mL / (m 2·day·atm), Mitsui Chemicals, Inc., TAKELAC WPB-341) and stirred. Then, dilution water was added so that the solid content concentration became 20% by mass to form a barrier layer coating liquid. A Meyer rod was used to coat the barrier layer in an amount of 2.0 g / m 2 After applying the barrier layer coating liquid in a manner, the barrier layer was dried in a hot air dryer at 120° C. for 1 minute to form a barrier layer.

[0456] <Formation of sealing layer>

[0457] A sealing layer was provided in the same manner as in Example 2-4 to obtain ultraviolet laser printing paper.

[0458] [Example 2-32]

[0459] <Manufacturing of paper substrate, preparation of coating liquid and formation of printed layer>

[0460] A printed layer was formed on the paper base layer in the same manner as in Example 2-4.

[0461] <Formation of barrier layer>

[0462] On aluminum-deposited PP film (substrate = CPP (unstretched polypropylene film), manufactured by Mitsui Chemicals Tohcello, Inc., product name: ML, thickness 20 μm, water vapor transmission rate 0.2 g / m 2 day, oxygen permeability 50mL / m 2 ·day·atm) of the PP film side, at 5g / m 2 After applying an isocyanate adhesive (10 parts of DICDRY LX-500 manufactured by DIC Corporation, mixed with 1 part of DICDRY KW-75 manufactured by DIC Corporation), the adhesive was bonded to the surface of the paper substrate opposite to the surface provided with the printed layer.

[0463] <Formation of sealing layer>

[0464] A sealing layer was formed in the same manner as in Example 2-4 to obtain ultraviolet laser printing paper.

[0465] [Example 2-33]

[0466] In forming the barrier layer, an aluminum-deposited PET film (substrate = PET (polyethylene terephthalate), manufactured by Mitsui Chemicals Tohcello, Inc., product name: ML, thickness 12 μm, water vapor transmission rate 1 g / m 2 day, oxygen permeability 10mL / m 2·day·atm), except that the ultraviolet laser printing paper was obtained in the same manner as in Example 2-32. It should be noted that the adhesive was applied on the substrate (PET) side.

[0467] [Example 2-34]

[0468] For the formation of the barrier layer, a silica-deposited PP film (substrate = PP, manufactured by Toppan Printing Co., Ltd., product name: GL-LP, thickness 17 μm, water vapor transmission rate 0.5 g / m 2 day, oxygen permeability 1mL / m 2 ·day·atm), except that the ultraviolet laser printing paper was obtained in the same manner as in Example 2-32. It should be noted that the adhesive was applied on the substrate (PP) side.

[0469] [Example 2-35]

[0470] For the formation of the barrier layer, a silica-deposited PET film (substrate = PET, manufactured by Toppan Printing Co., Ltd., product name: GL-AE, thickness 12 μm, thickness of the deposited layer 400 nm, water vapor transmission rate 0.6 g / m 2 day, oxygen permeability 0.2mL / m 2 ·day·atm), except that the ultraviolet laser printing paper was obtained in the same manner as in Example 2-32. It should be noted that the adhesive was applied on the substrate (PET) side.

[0471] [Example 2-36]

[0472] In forming the barrier layer, an alumina-deposited PET film (substrate = PET, manufactured by Mitsui Chemicals Tohcello, Inc., product name: TL, thickness 12 μm, water vapor transmission rate 1.5 g / m 2 day, oxygen permeability 15mL / m 2 ·day·atm), except that the ultraviolet laser printing paper was obtained in the same manner as in Example 2-32. It should be noted that the adhesive was applied on the substrate (PET) side.

[0473] [Example 2-37]

[0474] For the formation of the barrier layer, a PET film coated with PVDC (polyvinylidene chloride) (Mitsui Chemicals Tohcello, Inc., product name: VBARRIER, thickness 12 μm, water vapor transmission rate 0.2 g / m 2 day, oxygen permeability 0.8mL / m 2·day·atm), except that the ultraviolet laser printing paper was obtained in the same manner as in Example 2-32. It should be noted that the adhesive was applied on the substrate (PET) side.

[0475] [Comparative Example 2-3]

[0476] <Preparation of coating solution>

[0477] As shown in Table 3, 68 parts of titanium oxide D and 32 parts of ion exchange water were mixed to a solid content concentration of 68%. Then, a pigment dispersion was prepared using a Cowles disperser, and 42,980 parts (15,043 parts in terms of solid content) of an ethylene-acrylic emulsion (CHEMIPEARL S-300 manufactured by Mitsui Chemicals, Inc., solid content concentration 35%) was added as an emulsion to prepare a coating liquid with a solid content concentration of 35.9%. Then, the coating liquid was diluted with ion exchange water to adjust the solid content concentration to 35.1%.

[0478] Ultraviolet laser printing paper was obtained in the same manner as in Example 2-4 except that the printing layer was coated on a paper substrate so that the content of titanium oxide in the printing layer became the content (weight per unit area) described in Table 3.

[0479] [Reference Example 1]

[0480] Except that the seal layer was not formed, an ultraviolet laser printing paper was obtained in the same manner as in Example 2-4.

[0481] [Measurement / Evaluation]

[0482] The following measurements and evaluations were performed on the paper substrates and ultraviolet laser printing papers obtained in Examples and Comparative Examples, and various raw materials.

[0483] [Method for measuring the particle size of titanium oxide]

[0484] The average particle size of titanium oxide contained in the printed layer is calculated as follows: the printed layer is cut off from the ultraviolet laser printing paper obtained in the examples and comparative examples with an industrial razor (manufactured by FEATHER Safety Razor Co., Ltd., product number: 099769), and the collected printed layer is used as a sample, and the ash obtained by burning in a muffle furnace is obtained by SEM images (secondary electron images) obtained by scanning electron microscope (SEM, manufactured by Hitachi High-Tech Corporation, SU7000, etc.). The ash is obtained as follows: It is obtained by calcining and ashing at 450°C using a muffle furnace (manufactured by Yamato Scientific Co., Ltd., model FO300).

[0485] When it is clear that the layers other than the printed layer do not contain titanium oxide, the content can be calculated from a SEM image of the ash obtained by collecting the ultraviolet laser printing paper itself without cutting out the printed layer and sintering and ashing it in the same manner.

[0486] The sample of ash content tested in scanning electron microscope is made as follows: in an ultrasonic cleaning machine (AS ONE Co., Ltd., LSC-63, etc.), dispersed in ethanol for 5 minutes to obtain 0.1% by mass slurry, 0.1mL is cast on an aluminum dish, and dried at 100°C to make it. The particles that are clearly distinguished from the adjacent particles are visually selected, and the geometric mean of the major diameter and minor diameter of one particle is taken as the particle size. At this time, even if the primary particles and the secondary particles in the aggregated state are mixed, they will each be counted as one particle when clearly distinguished, and the average diameter of 100 randomly selected particles will be taken as the particle size. The magnification during SEM image observation is appropriately selected according to the particle size of titanium oxide, and is set to about 20,000 times. In addition, in the case of particles other than titanium oxide, the particles contained in the titanium element are measured using an energy dispersive X-ray analyzer attached to the SEM (manufactured by Horiba, Ltd., EMAX, etc.).

[0487] In the case of a needle-shaped particle, the major diameters of 100 particles were measured and the average was taken as the particle diameter.

[0488] 〔Crystalline size calculation method〕

[0489] <Measurement sample preparation method>

[0490] The ultraviolet laser printing paper obtained from the examples and comparative examples was cut off the printed layer with an industrial razor (manufactured by FEATHER Safety Razor Co., Ltd., product number: 099769), and the collected printed layer was used as a sample, and the ash content was calculated from the SEM image (secondary electron image) obtained by scanning electron microscope (SEM, manufactured by Hitachi High-Tech Corporation, SU7000, etc.) obtained by burning in a muffle furnace. The ash content was obtained as follows: using a muffle furnace (manufactured by Yamato Scientific Co., Ltd., model FO300), sintering at 450°C and ashing to obtain.

[0491] It should be noted that, when the printed layer is a laminated layer and does not have other layers, the ultraviolet laser printing paper is impregnated with a cellulase aqueous solution (Genencor, model: VISCAMYL FLOW, concentration 20% (used after dilution 2 times)) and left to stand at 40°C for 40 hours to dissolve the paper substrate and separate the printed layer. In this case, the separated printed layer is ashed to obtain ash.

[0492] <Measurement by X-ray diffraction>

[0493] The ashing test sample is filled into the sample holder and measured using a high-speed detector. When filling, a height adjustment jig is used appropriately according to the sample amount, thereby adjusting the sample measurement surface and the edge of the sample holder to the same height.

[0494] (Measurement conditions)

[0495] X-ray diffraction apparatus: RINT-Ultima III manufactured by Rigaku Corporation

[0496] Voltage: 40kV

[0497] Current: 40mA

[0498] Optics: Collimated Beam (CBO)

[0499] Detector: Rigaku Corporation, high-speed detector D / teX Ultra 2

[0500] Goniometer: Ultima III horizontal goniometer

[0501] Tube ball: Cu

[0502] wavelength: (Kα1)

[0503] Scan mode: CONTINUOUS

[0504] Scanning speed: 1.0000deg / min

[0505] Stepping range: 0.0500deg

[0506] Scan axis: 2Theta / Theta

[0507] Scanning range: 5.0000~60.0000deg

[0508] Entrance slit: 1.0mm

[0509] Length limit slit: 10mm

[0510] Light receiving slit 1: open

[0511] Light receiving slit 2: open

[0512] Sample holder: ASC-6 sample holder (product number 2455E442)

[0513] Material: Aluminum

[0514] size:

[0515] Bracket height adjustment fixture: transparent disc-shaped plate (self-made)

[0516] Material: Polymethyl acrylate

[0517] size:

[0518] <Processing of data obtained from X-ray diffraction>

[0519] The obtained diffraction profile was subjected to background processing and profile fitting processing using comprehensive powder X-ray analysis software (PDXL2 manufactured by Rigaku Corporation).

[0520] All data processing settings were performed under the default settings of the software unless otherwise specified.

[0521] The crystal phase was identified based on the information of the peak position and peak intensity of the diffraction profile, based on the database (ICDD).

[0522] <Calculation of crystallite size based on data obtained by X-ray diffraction>

[0523] The full width at half maximum (FWHM) and the Bragg angle (θ) of the strongest diffraction line obtained from the diffraction profile after data processing are substituted into the Scherrer equation to calculate the crystallite size.

[0524] The X-ray diffraction peaks of titanium oxide used for the calculation are as follows.

[0525] Anatase: 101 faces

[0526] Rutile: 110 faces

[0527] The Scherrer formula is as follows.

[0528] D=Kλ / B cosθ

[0529] D: Crystallite size (nm)

[0530] K: Scherrer constant

[0531] λ: wavelength of X-rays (nm)

[0532] B: FWHM (rad)

[0533] θ: Bragg angle (rad)

[0534] The value of K is 0.89, B is the value of FWHM obtained in the measurement, the value of λ is 0.154, and the value of θ is as follows: in the case of anatase, it is the measured value of the maximum intensity derived from the 101 plane, and in the case of rutile, it is the measured value of the maximum intensity derived from the 110 plane.

[0535] 〔CSF〕

[0536] The Canadian standard freeness (CSF) of raw pulp is measured in accordance with JIS P8121-2:2012.

[0537] [Basic weight of paper substrate]

[0538] As a pretreatment, the obtained ultraviolet laser printing paper was subjected to a grinding device (manufactured by Sagawa Seisakusho Co., Ltd., grindstone size 200 mm ... ) is removed by grinding.

[0539] Next, when there is a printing layer, a sealing layer, a barrier layer, etc. formed by coating, a part of these layers permeates into the paper base material. Therefore, the printing paper subjected to the above pretreatment is immersed in xylene at 100°C to dissolve the resin component.

[0540] The obtained paper substrate was humidity-conditioned for 1 day in an environment of 23° C. and 50% humidity. The basis weight of the sample after humidity conditioning was measured in accordance with JIS P 8124:2011.

[0541] 〔Thickness of paper substrate〕

[0542] The thickness of the paper substrate was measured in accordance with JIS P 8118: 2014. The thickness of the printed layer, barrier layer, heat seal layer, etc. was calculated from the SEM image as described below, and was calculated by subtracting the value measured in accordance with JIS P 8118: 2014.

[0543] [Length-weighted average fiber length, fiber width, and fine fiber content of pulp fibers constituting paper substrate]

[0544] The length-weighted average fiber length, fiber width, and fine fiber content of the pulp constituting the paper substrate were measured by the following methods.

[0545] The printing media of the examples and comparative examples were cut into 4 cm squares, and about 50 times by weight of ion exchange water was added thereto, followed by immersion for 24 hours.

[0546] After immersion for 24 hours, the pulp was treated with a standard disintegrator (manufactured by Kumagai Riki Kogyo Co., Ltd.) until undisintegrated fibers disappeared, thereby disintegrating the pulp into fibers. The disintegrated slurry (dispersion of pulp fibers) from which the sealant layer, and any barrier layer and resin layer were removed was classified, and the "length-weighted average fiber length (ISO)", "microfiber amount" and "fiber width" were measured using a fiber length measuring machine (model FS-5 with UHD base unit, manufactured by Valmet).

[0547] It should be noted that the "length-weighted average fiber length (ISO)" is the length-weighted average fiber length calculated by selecting fibers of 0.2 mm or more and 7.6 mm or less. In addition, the "microfiber amount" is the ratio of the number of microfibers with a fiber width of 75 μm or less and a length of 0.08 mm or more and 0.20 mm or less in the dissociated pulp fibers. The "fiber width" is the length-weighted average fiber width calculated by selecting fibers with a width of 10 μm or more and 75 μm or less.

[0548] 〔Water retention value〕

[0549] The ultraviolet laser printing papers of Examples and Comparative Examples were subjected to the following treatment as pretreatment before measurement.

[0550] The printed layer provided by coating, the sealing layer provided by coating, the barrier layer provided by coating, and the resin layer provided by coating were cut and removed with an industrial razor (manufactured by FEATHER Safety Razor Co., Ltd., product number: 099769). In addition, in the case of a sealing layer provided by lamination and a barrier layer provided by coating, the sealing layer and the barrier layer were cut and removed with an industrial razor (manufactured by FEATHER Safety Razor Co., Ltd., product number: 099769) during the pretreatment. Furthermore, in the case of a printed layer provided by coating and a resin layer provided by lamination, the printed layer and the lamination layer were also cut and removed in the same manner.

[0551] Then, ion exchange water in an amount of about 50 times the mass of the printing paper was added to the pre-treated printing paper and the paper was left to stand for 24 hours. After the paper was left to stand for 24 hours, the paper was treated with a standard disintegrator (manufactured by Kumagai Riki Kogyo Co., Ltd.) until the undisintegrated fibers disappeared, thereby disintegrating the pulp into fibers.

[0552] When the printing paper subjected to the dissociation treatment has any layer selected from the group consisting of a printing layer provided by lamination, a sealing layer provided by lamination, a barrier layer provided by lamination, and a resin layer provided by lamination which has not been removed by the pre-treatment, these lamination layers are removed from the dissociated slurry, and ion exchange water is added to adjust the concentration to 0.5%. Ion exchange water is added to the dissociated slurry (dispersion liquid of pulp fibers) to adjust the concentration to 0.5%.

[0553] The water retention value of the obtained pulp fibers was measured in accordance with JAPAN TAPPI No. 26 (2000) (Pulp - Water Retention Value Test Method).

[0554] 〔Titanium oxide content〕

[0555] 1. When the printing paper contains non-printable areas

[0556] (Preparation of test pieces)

[0557] The printable area and the non-printable area (area without a coating layer) of the printing paper were cut into appropriate sizes to prepare samples (test pieces), and the cut areas were recorded.

[0558] (Dissolution of test piece)

[0559] A mixed solvent of nitric acid: hydrofluoric acid = 50:5 (volume %) and a test piece were placed in a Teflon (registered trademark) container of an autoclave apparatus (manufactured by CEM Japan, MARS5), and the autoclave treatment was performed at 210°C for 120 minutes to dissolve the test piece. The area of ​​the test piece can be appropriately changed. In addition, when the test piece is dissolved and remains, the ratio of nitric acid and hydrofluoric acid, the treatment temperature, the treatment time, etc. can be appropriately changed.

[0560] After the test piece is dissolved, the volume is accurately adjusted with ultrapure water.

[0561] (Determination of the amount of titanium oxide in the solution)

[0562] (1) The ICP apparatus and measurement conditions are as follows.

[0563] ICP apparatus: ICP-OEC apparatus (manufactured by Rigaku Corporation, CIROS1-20)

[0564] Determination conditions:

[0565] Carrier gas: Argon

[0566] Argon gas flow rate 0.9L / min

[0567] Plasma gas flow rate 14L / min

[0568] Plasma output 1400W

[0569] Pump speed: 2

[0570] ·Measurement wavelength Ti: 334.941nm

[0571] (2) Preparation of standard curve

[0572] A universal mixed standard solution (manufactured by SPEX, XSTC-622B) was accurately measured to have the following concentration, and subjected to measurement under the above-mentioned measurement conditions to measure the intensity at 334.941 nm corresponding to the emission wavelength of titanium atoms.

[0573] ·Concentrations for standard curve preparation: 0ppm, 0.01ppm, 0.05ppm, 0.1ppm, 0.5ppm, 1.0ppm, 3.0ppm, 5.0ppm

[0574] (3) Determination of titanium oxide content in the solution

[0575] The solution in which the test piece was dissolved was diluted with ultrapure water so as to fall within the above-mentioned standard curve, and subjected to ICP measurement.

[0576] (4) Calculation method of titanium oxide content

[0577] The titanium oxide content was calculated using the following formula: It should be noted that the molecular weight of titanium oxide ÷ the atomic weight of titanium ≈ 1.669.

[0578] Titanium oxide content (g / m 2 )=ICP determination concentration (ppm)×dilution ratio×fixed volume (L)×1.669×1000÷area (m 2 )

[0579] The titanium oxide content in the coating layer was determined by subtracting the titanium oxide content in the unprintable region from the titanium oxide content in the printable region.

[0580] 2. When the printing paper contains non-printable areas

[0581] (Preparation of test pieces)

[0582] Cut two sheets of printing paper into appropriate sizes and record the cut areas.

[0583] One of the test pieces was cut and ground using a grinding machine (manufactured by Sagawa Seisakusho Co., Ltd., grinding stone size ), only the printed layer was cut off and removed as a control sample. It should be noted that, when there is also a resin layer on the printed layer, the resin layer was also removed in the same manner.

[0584] It is suitable to observe the cross section with an electron microscope so as not to cut away too much.

[0585] (Subsequent processing)

[0586] The same treatment as 1. was performed, and the difference in the titanium oxide content between the two sheets was taken as the titanium oxide content of the coating layer.

[0587] 〔Inorganic pigment content〕

[0588] The content of the inorganic pigment was measured in the same manner as the content of titanium oxide, except that the ICP measurement wavelength was changed to a measurement wavelength specific to the metal atom contained in each inorganic pigment. It should be noted that calcium was measured at a measurement wavelength of 422.673 nm and magnesium was measured at a measurement wavelength of 285.213 nm.

[0589] 〔Thickness of printed layer〕

[0590] The thickness of the printed layer was measured based on image data obtained by a scanning electron microscope.

[0591] (1) Preparation of measurement samples

[0592] The sample was embedded in a photocurable resin (D-800 manufactured by Toagosei Co., Ltd.), and the cross section of the printing medium was exposed using an ultramicrotome. A diamond knife was used for cutting at room temperature.

[0593] Gold was vapor-deposited to a thickness of about 20 nm on the cut cross section, and the cross section was subjected to measurement using a scanning electron microscope.

[0594] (2) Measurement equipment and conditions

[0595] Measuring device: S-3600 (manufactured by Hitachi High-Tech Corporation)

[0596] Measurement conditions: 2000 times magnification

[0597] The types of scanning microscopes are not limited to those described above, but devices of the types indicated by the scale bars are used.

[0598] When the printed layer is thin, select an appropriate magnification to obtain image data.

[0599] (3) Measurement method

[0600] After confirming that the observed printed layer contains titanium using an energy dispersive X-ray spectrometer attached to a scanning electron microscope, image data is obtained at a magnification of 2000 times. After printing the obtained image data on printing paper, the thickness of the printed layer of the object (the length of the boundary with the boundary of other layers) is measured with a ruler, and the thickness of the actual printed layer (coating layer or laminated layer) is measured compared with the scale. Image data of 5 parts randomly selected from 1 measurement sample are obtained, and the thickness of the thickest part of the printed layer and the thinnest part of the printed layer are measured from the image data of 1 part, and the average of the total 10 parts is taken as the thickness of the printed layer. It should be noted that the observation magnification can be changed according to the thickness of the observed printed layer.

[0601] It should be noted that, when a resin layer is further provided on the printed layer, the thickness of the resin layer can be measured by the same method. In addition, the thickness of the sealing layer and the barrier layer can also be measured in the same manner.

[0602] 〔Measurement of Raman spectroscopy〕

[0603] The Raman spectrum was measured by the following method. In the present example, the Raman spectrum was measured on a printed material obtained by printing one dot clarity described later.

[0604] <Measurement conditions>

[0605] The measurement conditions of Raman spectrum are as follows. When damage is visible in the printed material under the laser used in the measurement, when the fluorescence is strong, when the peak intensity is weak, etc., the following measurement conditions such as laser output and irradiation time can be appropriately changed. Among them, the Raman intensity of the printed area and the non-printed area is the value measured under the same conditions.

[0606] · Device: inVia Raman microscope QUONTOR manufactured by Renishaw Inc.

[0607] Excitation laser: 532nm

[0608] Laser power: 50mW (at 100% output)

[0609] Laser output: 10%

[0610] ·Measurement mode: Confocal mode

[0611] Irradiation time: 2.5 sec

[0612] Cumulative times: 50 times

[0613] Laser spot diameter: 2.5μm

[0614] Objective lens: 20 times

[0615] <Measurement method>

[0616] The measurement was performed according to the following method.

[0617] (1) Using a standard sample (single crystal silicon, manufactured by Renishaw Inc.), the Raman shift position was calibrated (520.5 cm for single crystal silicon). -1 ).

[0618] (2) Place a sheet sample on the sample stand and set a clamp as needed to keep the sheet flat.

[0619] (3) Use the device to observe the focus (set in a way that the focus becomes the smallest under the simulated laser). When measuring the printed area, measure in a way that the darkest part that can be visually confirmed appears in the center of the guide marked during measurement. When measuring the non-printing area, measure at a distance of 300μm or more from the printed area.

[0620] (4) The obtained Raman spectrum was subjected to baseline correction (smart correction) using the processing software (Wire 5.2 manufactured by Renishaw Inc.) attached to the device. The baseline was corrected using polynomial 11 in the processing software.

[0621] (5) In the case of rutile titanium oxide, the reading is 447±10cm -1 The maximum value (maximum intensity) of the wavenumber range is 516±10cm in the case of anatase titanium oxide. -1 The maximum value (maximum intensity) of the wavenumber range is taken and the Raman intensity ratio is calculated according to the following formula.

[0622] Raman intensity ratio = maximum intensity of the printed area ÷ maximum intensity of the non-printed area

[0623] (6) 10 locations were measured in each of the printing area (printing portion) and the non-printing area (non-printing portion), and the average value was used as the measurement result.

[0624] From the viewpoint of suppressing fluctuations in the measured value, it is preferred to measure within a range where the count of the Raman intensity in the printed area is 10,000 or less. Therefore, the measurement conditions are appropriately changed so that the count of the Raman intensity in the printed area is within a range of 10,000 or less. In addition, the measurement is performed 10 times under the following measurement conditions, and the values ​​deviating by more than the mean value ± 2SD (standard deviation) are excluded, and the average is taken again to obtain the average value of the Raman intensity.

[0625] The Raman intensity ratio was evaluated by the following A to C.

[0626] A: Raman intensity ratio is less than 0.3

[0627] B: Raman intensity ratio is more than 0.3 and less than 0.7

[0628] C: Raman intensity ratio exceeds 0.7

[0629] [Sharpness of printing 1 dot]

[0630] <Laser printing method>

[0631] For the substrates obtained in Examples and Comparative Examples, a 10 mm square was printed on the surface of the sample using an ultraviolet laser irradiator (manufacturer name: KEYENCE CORPORATION, model: MD-U1020C).

[0632] (Printing conditions)

[0633] Wavelength: 355nm

[0634] Output: 80% (2.5W at 100% output)

[0635] Frequency: 40kHz

[0636] Focus distance: 300mm (focusing is performed using the height correction included with the device)

[0637] Spot diameter: 40μm (when focused)

[0638] Entire surface coating interval: 0.3mm

[0639] Scanning speed: 5000mm / sec

[0640] Points changeable: 100

[0641] It should be noted that only Examples 1-22 and 2-22 were implemented at an output of 40%.

[0642] <Evaluation of the clarity of printing 1 point>

[0643] Using a digital microscope (manufacturer name: KEYENCE CORPORATION, model: VHX-8000), a depth composite image of the vicinity of the printed portion of the evaluation object was obtained ( Figure 2A and Figure 2B ). A depth composite image is an image that is constructed by obtaining multiple images by moving the focus distance and extracting the in-focus parts from each image. The depth composite image is obtained using the real-time depth composite function installed in the digital microscope.

[0644] It should be noted that Figure 2A is the depth synthesis image of Comparative Example 1-2, Figure 2B It is the depth synthesis image of Example 1-4.

[0645] Then, the area of ​​the printed area that is darker than the threshold is measured using the brightness extraction mode in the automatic area measurement function. The brightness extraction mode is a mode that extracts areas above or below a certain threshold by grading the brightness level of the image from -255 to 255. For the printed area, the more areas with brightness levels below the threshold, the darker the print.

[0646] (Settings when shooting images)

[0647] Shutter speed: Automatic mode (setting value 70)

[0648] Gain: 0dB

[0649] Magnification: 1000 times

[0650] Lighting: Ring lighting

[0651] (Brightness extraction mode settings)

[0652] Magnification when deep composite image is obtained: 1000 times

[0653] Illumination: Coaxial incident light 100%

[0654] Shutter speed: Auto mode 70

[0655] Gain: 0dB

[0656] Threshold: -10

[0657] Extraction area: Inside the circle with a radius of 50 μm from the center of the printed part

[0658] (Evaluation criteria for the depth of the printed part)

[0659] A: The area with brightness level lower than -10 is more than 70% of the extraction area

[0660] B: The area of ​​the region with a brightness level lower than -10 is 65% or more and less than 70% of the extraction area

[0661] C: The area of ​​the region with a brightness level lower than -10 is 60% or more and less than 65% of the extraction area

[0662] D: The area of ​​the region with a brightness level lower than -10 is 40% or more and less than 60% of the extraction area

[0663] E: The area of ​​the region with brightness level below -10 is less than 40% of the extracted area

[0664] 〔Printing uniformity〕

[0665] For the ultraviolet laser printing papers obtained in Examples and Comparative Examples, a square of 10 mm square was printed on the surface of the sample using an ultraviolet laser irradiator (manufacturer name: KEYENCE CORPORATION, model: MD-U1020C).

[0666] (Printing conditions)

[0667] Wavelength: 355nm

[0668] Output: 80% (2.5W at 100% output)

[0669] Frequency: 40kHz

[0670] Focus distance: 300mm (focusing is performed using the height correction included with the device)

[0671] Spot diameter: 40μm (when focused)

[0672] Entire surface coating interval (line spacing): 0.05mm

[0673] Scanning speed 3000mm / sec

[0674] Points changeable: -100

[0675] (Printing uniformity evaluation)

[0676] 100 squares were printed, and the printing uniformity was evaluated based on the number of squares with visually recognizable differences in depth (printing unevenness) in one square, according to the following criteria.

[0677] A: For 100 squares, the number of squares with different depths is less than 3.

[0678] B: For 100 squares, the number of squares with different depths is more than 3 and less than 5.

[0679] C: For 100 squares, the number of squares with different depths is greater than 5 and less than 10.

[0680] D: For 100 squares, the number of squares with different depths is more than 10.

[0681] 〔Dust generation〕

[0682] When evaluating printing uniformity, the amount of dust generated when a square of 10 mm×10 mm was printed on the surface of a sample by ultraviolet laser irradiation was evaluated according to the following criteria.

[0683] (Judgment Criteria)

[0684] A: The dust generation cannot be visually confirmed, or the dust generation can be vaguely confirmed but very small.

[0685] B: Dust generation can be visually confirmed, but the amount of dust generated is small

[0686] C: Dust generation can be visually confirmed, but it has little impact on printing

[0687] D: Dust generation can be easily confirmed visually. The dust generation scatters the light of the ultraviolet laser. The amount of dust generation is so large that it affects printing.

[0688] 〔Water vapor barrier properties〕

[0689] The water vapor barrier properties of the printing papers obtained in Examples 2-1 to 2-37, Comparative Examples 2-1 to 2-3, and Reference Example 2-1, each having a sealant layer, were evaluated in accordance with JIS-Z-0208:1976 (cup method) B method (40°C ± 0.5°C, relative humidity 90% ± 2%) with the sealant layer facing inside.

[0690] The water vapor barrier properties were evaluated according to the following evaluation criteria.

[0691] (Evaluation criteria for water vapor barrier properties)

[0692] A: Water vapor transmission rate is 30g / m 2 ·Day or less

[0693] B: Water vapor transmission rate exceeds 30g / m 2 day and 40g / m 2 ·Day or less

[0694] C: Water vapor transmission rate exceeds 40g / m 2 day and 50g / m 2 ·Day or less

[0695] D: Water vapor transmission rate exceeds 50g / m 2 ·day

[0696] Laser irradiation was performed under the following conditions, and the water vapor permeability of the ultraviolet laser printed material after laser irradiation was similarly measured. Note that, for Reference Example 2-1, the water vapor barrier property before ultraviolet laser irradiation was evaluated as D, and therefore was not measured.

[0697] <Laser irradiation>

[0698] For the ultraviolet laser printing papers obtained in Examples 2-1 to 2-37 and Comparative Examples 2-1 to 2-3, a 10 cm square was printed on the sample surface (printing layer side) using an ultraviolet laser irradiator (manufacturer name: KEYENCE CORPORATION, model: MD-U1020C) under the following conditions.

[0699] Printing conditions

[0700] Wavelength: 355nm

[0701] Output: 80% (2.5W at 100% output)

[0702] Frequency: 40kHz

[0703] Focus distance: 300mm (focusing is performed using the height correction included with the device)

[0704] Spot diameter: 40μm (when focused)

[0705] Entire surface coating interval: 0.04mm

[0706] Scanning speed 1000mm / sec

[0707] Points Variable: 0

[0708] 〔Oxygen barrier properties〕

[0709] The oxygen permeability of the ultraviolet laser printing papers of Examples 2-29 to 2-37 was measured at a temperature of 23° C. and a relative humidity of 85% using an oxygen permeability measuring apparatus (OX-TRAN 2 / 22 manufactured by MOCON Corporation).

[0710] Specifically, about the laminated sheet, the oxygen permeability at a temperature of 23° C. and a relative humidity of 85% was measured in accordance with JIS K7126-2:2006.

[0711] The lower the value of the oxygen permeability, the better the oxygen barrier property.

[0712] The oxygen barrier properties were evaluated according to the following evaluation criteria.

[0713] (Evaluation criteria for oxygen barrier properties)

[0714] A: Oxygen permeability is 3.0mL / m 2 ·day·atm or less

[0715] B: Oxygen permeability exceeds 3.0mL / m 2 ·day·atm and 5.0mL / m 2 ·day·atm or less

[0716] C: Oxygen permeability exceeds 5.0 mL / m 2 ·day·atm and 15mL / m 2 ·day·atm or less

[0717] D: Oxygen permeability exceeds 15mL / m 2 ·day·atm

[0718] In addition, laser irradiation was performed under the following conditions, and the oxygen permeability of the ultraviolet laser printed matter after laser irradiation was similarly measured.

[0719] <Laser irradiation>

[0720] The ultraviolet laser printing papers obtained in Examples and Comparative Examples were printed with an ultraviolet laser irradiator (manufacturer name: KEYENCE CORPORATION, model: MD-U1020C) on the sample surface (printing layer side) in a square shape of 10 cm under the following conditions.

[0721] Printing conditions

[0722] Wavelength: 355nm

[0723] Output: 80% (2.5W at 100% output)

[0724] Frequency: 40kHz

[0725] Focus distance: 300mm (focusing is performed using the height correction included with the device)

[0726] Spot diameter: 40μm (when focused)

[0727] Entire surface coating interval: 0.04mm

[0728] Scanning speed 1000mm / sec

[0729] Points Variable: 0

[0730] [Barrier reduction rate after ultraviolet laser irradiation (barrier reduction rate)]

[0731] The reduction in barrier properties (barrier property reduction rate) due to ultraviolet laser irradiation was evaluated based on the water vapor transmission rate and oxygen transmission rate before and after ultraviolet laser irradiation according to the following evaluation criteria.

[0732] (Evaluation criteria for barrier property reduction rate)

[0733] A: The reduction rate (reduction rate) of water vapor transmission rate and oxygen transmission rate is 5.0% or less

[0734] B: The reduction rate (reduction rate) of water vapor transmission rate or oxygen transmission rate exceeds 5.0%

[0735] In addition, the reduction rate of water vapor transmission rate was calculated as follows.

[0736] Water vapor transmission rate reduction rate = (water vapor transmission rate after ultraviolet laser irradiation (g / m 2·day)-Water vapor transmission rate before UV laser irradiation (g / m 2 ·day)) / Water vapor transmission rate before UV laser irradiation (g / m 2 ·day)×100

[0737] Similarly, the reduction rate of oxygen permeability was calculated as follows.

[0738] Oxygen permeability reduction rate = (oxygen permeability after ultraviolet laser irradiation (mL / m 2 ·day·atm)-oxygen permeability before ultraviolet laser irradiation (mL / m 2 ·day·atm)) / oxygen permeability before ultraviolet laser irradiation (mL / m 2 ·day·atm)×100

[0739] [Heat seal peel strength and heat seal peel strength reduction rate (peel strength reduction rate)]

[0740] Two sets of ultraviolet laser printing papers were overlapped with the sealing layers facing each other, and heat-sealed using a heat seal tester (Tester Industrial, TP-701-B) at 160°C, 0.2 MPa, and 1 second. The heat-sealed test piece was left to stand in a room at a temperature of 23°C ± 1°C and a humidity of 50% ± 2% for more than 4 hours. Then, the heat-sealed test piece was cut into a width of 15 mm, and a T-peel was performed using a tensile tester at a tensile speed of 300 mm / min, and the maximum load recorded was taken as the heat seal peel strength.

[0741] The heat seal peel strength was evaluated according to the following evaluation criteria.

[0742] (Evaluation criteria for heat seal peel strength)

[0743] A: Heat seal peel strength is above 10N / 15mm

[0744] B: Heat seal peel strength is 6.0N / 15m or more and less than 10N / 15mm

[0745] C: Heat seal peel strength is 3.0N / 15mm or more and less than 6.0N / 15mm

[0746] D: Heat seal peel strength is less than 3.0N / 15mm

[0747] <Laser irradiation>

[0748] The ultraviolet laser printing papers obtained in Examples and Comparative Examples were printed with an ultraviolet laser irradiator (manufacturer name: KEYENCE CORPORATION, model: MD-U1020C) on the sample surface (printing layer side) in a square shape of 10 cm under the following conditions.

[0749] Printing conditions

[0750] Wavelength: 355nm

[0751] Output: 80% (2.5W at 100% output)

[0752] Frequency: 40kHz

[0753] Focus distance: 300mm (focusing is performed using the height correction included with the device)

[0754] Spot diameter: 40μm (when focused)

[0755] Entire surface coating interval: 0.04mm

[0756] Scanning speed 1000mm / sec

[0757] Points Variable: 0

[0758] (Evaluation criteria for heat seal peel strength reduction rate)

[0759] The reduction in barrier properties (barrier property reduction rate) due to ultraviolet laser irradiation was evaluated based on the heat seal peel strength before and after ultraviolet laser irradiation according to the following evaluation criteria. It should be noted that for Comparative Example 2-4, the heat seal peel strength before ultraviolet laser irradiation was evaluated as D, so it was not measured.

[0760] (Evaluation Criteria for Reduction Rate of Heat Seal Peel Strength)

[0761] A: The reduction rate (reduction rate) of heat seal peel strength is 5.0% or less

[0762] B: The reduction rate (reduction rate) of heat seal peel strength exceeds 5.0%

[0763] In addition, the reduction rate of heat seal peel strength was calculated as follows.

[0764] Heat seal peel strength reduction rate = (heat seal peel strength before UV laser irradiation (N / 15mm) - heat seal peel strength before UV laser irradiation (N / 15mm)) / heat seal peel strength before UV laser irradiation (N / 15mm) × 100

[0765] [Table 2]

[0766]

[0767] [Table 3-1]

[0768]

[0769] [Table 3-2]

[0770]

[0771] From the results in Table 2, it can be seen that a printed product having a printed image with excellent print clarity per dot can be obtained by printing with an ultraviolet laser using the printing paper of the example.

[0772] In the printing paper of Example 1-6 using titanium oxide having a relatively large crystallite size of 55.3 nm, a decrease in printing uniformity was observed, which was considered to be accompanied by a decrease in the dispersion stability of titanium oxide.

[0773] When the printing papers of Comparative Examples 1-1 and 1-2 containing titanium oxide with a crystallite size of less than 30 nm were used, even when printing was performed using an ultraviolet laser, a printed image with poor print clarity per dot was obtained. In addition, the content of titanium oxide in the printed layer was less than 0.1 g / m 2 In the printing papers of Comparative Examples 1-3, sufficient print clarity per dot could not be obtained.

[0774] From the results in Table 3, it can be seen that printing with the ultraviolet laser using the printing paper of the example can provide a printed product having a printed image with excellent print clarity per dot.

[0775] Furthermore, it has heat sealability and excellent water vapor barrier properties. In addition, the ultraviolet laser printing paper of Examples 2-29 to 2-37 in which a barrier layer is formed also has excellent oxygen barrier properties. In addition, the reduction in barrier properties and heat sealability due to printing using ultraviolet laser is suppressed.

[0776] In the printing paper of Example 2-6 using titanium oxide having a relatively large crystallite size of 55.3 nm, a decrease in printing uniformity was observed, which was considered to be accompanied by a decrease in the dispersion stability of titanium oxide.

[0777] When the printing papers of Comparative Examples 2-1 and 2-2 containing titanium oxide with a crystallite size of less than 30 nm were used, even when printing was performed by ultraviolet laser, a printed image with poor print clarity per dot was obtained. In addition, the content of titanium oxide in the printed layer was less than 0.1 g / m 2 In the printing paper of Comparative Example 2-3, sufficient print clarity at each point could not be obtained.

[0778] In addition, when the printing paper of Reference Example 2-1 having no sealant layer was used, heat sealability and water vapor barrier properties could not be obtained.

[0779] Industrial Applicability

[0780] The printing paper of the present invention changes color of titanium oxide by irradiation with an external laser, thereby providing a printed matter with excellent visibility and excellent print clarity per dot. The ultraviolet laser printing paper of the present invention is suitable for processed products such as packaging bodies, labels, and adhesive tapes printed with variable information such as dates and bar codes. Furthermore, the method for producing printed matter of the present invention is suitable for printing variable information on packaging bodies, labels, adhesive tapes, etc.

Claims

1. A UV laser printing paper having a printing layer containing titanium oxide on a paper substrate, The content of titanium oxide in the printed layer is 0.1 g / m 2 above, The crystallite size of titanium oxide in the printed layer is 30 nm or more.

2. The ultraviolet laser printing paper according to claim 1, wherein: The crystallite size of the titanium oxide is less than 53 nm.

3. The ultraviolet laser printing paper according to claim 1, wherein: The titanium oxide in the printed layer is rutile titanium oxide, and the diffraction angle of the titanium oxide is 27.60° or less.

4. The ultraviolet laser printing paper according to claim 1, wherein: The length-weighted average fiber length of the pulp constituting the paper substrate is 2.0 mm or less.

5. The ultraviolet laser printing paper according to claim 1, wherein: The content of titanium oxide in the printed layer is 10 g / m 2 the following.

6. The ultraviolet laser printing paper according to claim 1, wherein: Among the pulp fibers constituting the paper substrate, the number ratio of fine fibers having a fiber length of 0.2 mm or less is 4% or more and 40% or less.

7. The ultraviolet laser printing paper according to claim 1, wherein: The water retention value of the pulp fibers constituting the paper substrate is 100% or more.

8. The ultraviolet laser printing paper according to claim 1, wherein: The paper substrate has a sealing layer on the surface opposite to the surface having the printed layer.

9. The ultraviolet laser printing paper according to claim 1, further comprising a barrier layer.

10. A printed matter obtained from the ultraviolet laser printing paper according to any one of claims 1 to 9, wherein: The printed layer has a printed area containing discolored titanium oxide in at least a portion thereof, The ratio of the Raman intensity derived from titanium oxide in the printed area to the Raman intensity derived from titanium oxide in the non-printed area is 0.70 or less.

11. A processed product, which is obtained by using the ultraviolet laser printing paper according to any one of claims 1 to 9.

12. A processed product obtained by using the printed matter according to claim 11.

13. A method for producing a printed matter, comprising the following steps: The ultraviolet laser printing paper according to any one of claims 1 to 9 is irradiated with ultraviolet laser light to change the color of the irradiated area, thereby performing printing.

14. The method for producing a printed matter according to claim 13, wherein: The step of printing is a step of irradiating with ultraviolet laser light so that the ratio of the Raman intensity derived from titanium oxide in the printing area to the Raman intensity derived from titanium oxide in the non-printing area becomes 0.70 or less.

15. An ink composition for forming a printed layer that changes color when irradiated with ultraviolet laser, the printed layer containing titanium oxide having a crystallite size of 30 nm or more.

16. The ink composition according to claim 15, wherein The crystallite size of the titanium oxide is less than 53 nm.

17. The ink composition according to claim 15 or 16, wherein The titanium oxide is rutile titanium oxide, and the diffraction angle of the titanium oxide is less than 27.60°.

Citation Information

Patent Citations

  • Laminate for laser printing and print thereof

    JP1997123607A

  • Adhesive tape

    JP2012057112A

  • Talc master batch and manufacturing method therefor

    JP2015096568A

  • Ink composition, ultraviolet laser marking material, manufacturing method of material with laser marking, manufacturing method of package, manufacturing method of article with label for printing, and laser marking method

    JP2020075943A

  • Polyurethane dispersion and polyurethane laminate

    WO2015016069A1